Integration of clinical and cellular lipidomics identifies a serum metabolite signature predictive of oxaliplatin resistance in colorectal cancer - Xue-fei Wu; Li-ye Xie; Fu-wei Lian; Hao-tang Wei; Shu-fang Ning; Bang-li Hu (Functional & Integrative Genomics, 2026)

Seasonal grazing drives complementary adaptive strategies in grasses and forbs via niche divergence: Evidence from a long-term experiment in alpine meadows - Peng Jiang; Hao-Zhe Zheng; Qing-Shan Fan; Lu-Ji Ade; Shu-Lin Wang; Fu-Jiang Hou (Agriculture, Ecosystems & Environment, 2026)

Influence mechanism of tritium exposure on the growth and microcystin synthesis of Microcystis aeruginosa under rising temperature - Xue Gong; Xin-wen Zhang; Ling-shu Xu; Chuan-dong Wang; Bao Zhang; Qian Fu; Qi-lin Dai; Jin-long Lai (Environmental Pollution, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Phenethyl isothiocyanate mediates autophagy via the AMPK/mTOR signal pathway in human glioblastoma multiforme cells - Shu-Fen Peng; Hsin-Chung Liu; Fu-Shin Chueh; Hsu-Tung Lee; Sheng-Yao Hsu; Jaw-Chyun Chen; Jing-Gung Chung; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Waste soy milk-derived biodegradable seed coating agent: Synthesis, growth-promotion and drought resistance - Dongqing Cai; Cun Jiang; Bingbing Fu; Shihu Shu; Dongfang Wang; Pan Zhao; Yanping Zhu (Journal of Environmental Chemical Engineering, 2026)

Metal-polyphenol network-coated probiotic microcapsules: Enhancing Limosilactobacillus fermentum storage stability and yogurt characteristics - Yi-han Cai; Fang Huang; Si-ying Yan; Xiao-jin Lin; Shu-ling Huang; Shao-fu Feng; Jie-ying Chen; Yan-yan Huang; Xin-An Zeng; Xiang-ze Jia (International Dairy Journal, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

LsS6K acts as a negative regulator of thiamethoxam tolerance in Laodelphax striatellus - Shu Fang; Yuyang Shi; Mi Zhou; Huijun Zhang; Hong Fu; Qun Zheng; Kun Qian; Jianjun Wang (Pesticide Biochemistry and Physiology, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

pH-dependent interaction between Gallic acid and mung bean globulin amyloid fibrils: effects on interfacial behavior and emulsifying properties - Peng Jiang; Qingpeng Xu; Shu Zhang; Tianxin Fu; Yuhan Wang; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Research International, 2026)

Reemissions of polycyclic aromatic compounds from soil to air in chemical industrial parks - Yousong Zhou; Lu Yu; Kai Xiao; Donglei Fu; Ke Jiang; Jinmu Luo; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Differentiated provisioning in a mobile royal camp: zooarchaeological and stable isotope evidence from Houmingzi, a locality within a Liao–Jin spring nabo site complex, Northeast China - Wuyu Zhou; Yuanyuan Chen; Shu Wang; Zongyu Li; Yunxin Fu; Enxue Feng; Chunxue Wang; Song Wu (Archaeological and Anthropological Sciences, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

An injectable gas-enzyme cascade hydrogel for coordinating dual-lineage regeneration in diabetic rotator cuff repair - Yaqi Hua; Wenqi Duan; Rumin Fu; Runhui Liu; Yuan Shu; Wei Xu; Liang Hao (Chemical Engineering Journal, 2026)

Angstrom confined ion transport in graphene oxide membranes enables highly reversible zinc anodes - Lin Huang; Yihao Xu; Teng Deng; Shu Liu; Liping Chen; Yonghong Fu; Lei Dong; Juan Wang; Keyu Xie (Chemical Engineering Journal, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

Genome-wide identification of the WOX gene family in Capsicum baccatum and the roles of CbWOX7 and CbWOX9 in promoting callus proliferation - Yu Zhang; Muhammad Imran; Huangying Shu; Liping Zhang; Huazheng Shao; Yingsai Li; Xu Lu; Shanhan Cheng; Huizhen Fu; Zhiwei Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Novel sesquiterpenoids from Colletotrichum camelliae LP76, a predominant endophytic fungus from Camellia taliensis - Xiaoman Fu; Yuancao Shu; Zhiyu Zhang; Weihua Wang; Sida Xie; Xiaoqin Yang; Yingjun Zhang; Ping Zhao; Guolei Zhu (Natural Product Research, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

Data-driven slope stability prediction based on Gaussian process - Guorong Yu; Bingjie Fu; Shu Li; Haizhou Bao (Stochastic Environmental Research and Risk Assessment, 2026)

A CRISPR/dCas9 mediated electrochemical impedimetric biosensor for sensitive mtDNA detection - Fei Chen; Mengqin Huang; Shu Zeng; Yi Wan; Anjun Qin; Xinzhe Yang; Danfeng Fu; Masoud Negahdary; Chenghui Zhang (Analytica Chimica Acta, 2026)

Data Fusion Framework for a High-Resolution Regional Dataset in the Western North Pacific - Lifu Fu; Chunling Zhang; Yijun Ge; Bo Shu; Ruoxiao Zhou (Journal of Marine Science and Engineering, 2026)
Based on the large volume of observational data obtained from Argo and several satellites, an increasing number of datasets are being developed and applied to oceanographic research. However, there are still problems such as sparse subsurface observations, insufficient parameters, and weak pertinence. This study provides a basic framework for high-resolution data fusion that focuses on the multi-source observations in the Western North Pacific. Multi-source observations from satellites, Argo floats, and historical in situ profiles are fused using a statistical model and a gradient-dependent optimal interpolation method. A daily gridded dataset with a 0.25° horizontal resolution is developed, which includes temperature, salinity, and currents. The results show that the correlation coefficients between the observations and the inverted profiles of temperature and salinity are about 0.99 and 0.94, respectively, with mean root mean square errors of about 1.27 °C and 0.13, respectively. In the Northwest Pacific Ocean, the most suitable parameter settings are a search radius of 1.5° in longitude and latitude, correlation scale constant of 0.25°, and relative observation error of 2. Consequently, the average RMSEs of the fused temperature and salinity fields are 0.43°C and 0.056, respectively. Compared with other reanalysis datasets, the product constructed in this study retains more high-frequency ocean signals, and its temperature error relative to XBT observations is also the smallest. Furthermore, the dataset effectively depicts the characteristics of marine dynamic processes such as the Kuroshio paths and mesoscale eddies.

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Transcriptome analysis revealed the characteristics of the terpenoid biosynthesis pathways and discovered two TPS-b genes in Freesia × hybrida - Shidan Weng; Xueqing Fu; Shu Li; Yu Gao; Dongshi Li; Dongqin Tang (South African Journal of Botany, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Emissions of nitrogen oxide from household gaseous cooking - Yongqiang Zhang; Jian Fu; Tianyao Huang; Jieyang Gao; Hanchen Wang; Ke Jiang; Ran Xing; Guofeng Shen; Shu Tao (Environmental Pollution, 2026)

Cutaneous adverse events associated with Rybrevant based on FDA adverse event reporting system (FAERS) database from 2021 to 2024 - Yuqin Zeng; Yidan Li; Ziye Du; Risheng Shu; Chuhan Fu; Qinghai Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

A damage constitutive model for brittle rock considering compaction effect and energy dissipation characteristics - Jiale Fu; Shu Jiang; Linhao Zhang; Pengfei Xiong; Hongji Liu; Ruyang Yu; Zhiping Zhang (Computers and Geotechnics, 2026)

Molecular characterization of SnRK2 gene family in Capsicum chinense and functional validation of CcSnRK2.5 under drought stress - Huangying Shu; Yu Zhang; Jiancheng Liu; Liping Zhang; Xu Lu; Zhoubin Liu; Shanhan Cheng; Huizhen Fu; Zhiwei Wang (Plant Cell Reports, 2026)

Integrating GWAS and genomic selection with SNP and SV markers for enhanced prediction of complex traits in common carp - Xiaoyue Zhu; Yuhan Fu; Zhipeng Sun; Ruixin Zhang; Xianhu Zheng; Yongjun Shu; Guo Hu (Aquaculture, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Efficient saponin glycosidases of Aspergillus tubingensis HG57 enable green diosgenin production using Dioscorea zingiberensis tubers - Yulong Chen; Zhiyuan Chen; Tong Shu; Zhikuan Wang; Chunhua Fu; Longjiang Yu (Bioresource Technology, 2026)

Investigating the failure mechanism of a landslide triggered by the combined effects of excavation and rainfalls through numerical approaches - Shu-wei Sun; Xin-yu Fu; Yuan Li; Qiang Wen; Run-jie Gong (Landslides, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Occurrence and sources of organic contaminants of emerging concern in indoor dust: A global perspective - Wei Du; Ruijing Hu; Nan Fu; Min Wu; Yang Liu; Yuanchen Chen; Guofeng Shen; Nan Lin; Bo Pan; Shu Tao (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Construction of dual S-scheme WO3/g-C3N4/Bi4O5I2 heterojunctions for efficient bactericidal and BPA degradation under LED light - Jun Huang; Pitao Liu; Shuangxiu Shu; Sibei Fu; Yeping Li; Yanling Li; Li Qiu; Yanyan Fu; Liying Huang; Lijing Huang (Journal of Environmental Chemical Engineering, 2026)

NMR-based quantitative characterization and predictive modeling of adsorbed and free methane in deep coal reservoirs - Xinyu Fu; Shida Chen; Fan Yang; Shu Tao; Litao Ma; Cheng Liu; Jianghao Yang; Yi Cui; Qinghe Jing; Wei Gao (Fuel, 2026)

A high-strength, heat-resistant, recyclable, and degradable ramie fiber-reinforced polyimine biocomposite - Pandeng Li; Tingting Liu; Gen Lu; Tong Shu; Tianyi Yu; Yuchen Zhao; Hengwei Fu; Junqi Yang; Haoping Du; Penghao Sun; Ziqi Hou; Chunhua Fu; et al. (Chemical Engineering Journal, 2026)

Chemical armed allies promote plant resistance to pathogen: The contribution of arbuscular mycorrhizal fungi to an invasive weed - Shanshan Qi; Zhixiang Shu; Misbah Naz; Ying Li; Ruike Zhang; Guangqian Ren; Deli Zhai; Wei Wei; Weiguo Fu; Zhicong Dai; Daolin Du (Mycorrhiza, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

The glutamyl-prolyl-tRNA synthetase 1 inhibitor halofuginone exerts synergistic antitumor effects with bortezomib in colon cancer cells - Han Lin; Ying Yan; Chenyu Qiu; Junqi Wang; Wenying Fu; Chongchong Shu; Yinghua Chen; Chenxin Xu; Shaotang Li; Yiqun Xia; Jundixia Chen; Yunzhi Chen; et al. (Toxicology and Applied Pharmacology, 2026)

Monoculm1 confers cold tolerance at the seedling stage in rice - Ruiqing Li; Chenfan Zheng; Binqiang Wang; Shang Dai; Yue Song; Huali Zhang; Zhiguo E; Bo Liu; Jiale Chen; Can Zhang; Haowei Fu; Ning Xu; et al. (Molecular Plant, 2026)

Incomplete lineage sorting, hybridization and polyploidization blurred phylogenetic relationships of gentians from the Qinghai-Tibetan Plateau - Shan-Shan Sun; Shu-Han Xu; Wen-Jie Yi; Shi-Long Chen; Pan Li; Daiki Takahashi; Harue Abe; Xiao-Lei Ma; Peng-Cheng Fu (Molecular Phylogenetics and Evolution, 2026)

UVB enhances SLC6A15-mediated phenylalanine transport to promote melanogenesis - Shu Zhou; Yujie Ouyang; Yibo Hu; Xixia Dai; Ling Jiang; Chuhan Fu; Yaqing Wen; Jiangfeng Huang; Keyi Zhang; Jing Chen; Qinghai Zeng (Journal of Photochemistry and Photobiology B: Biology, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Prenatal and postnatal exposure to environmental level arsenic declines male reproductive function by affecting spermatogenesis and maturation in offspring - Xiaochao Song; Xu Yang; Weixiang Fu; Ying Xing; Chenkai Cheng; Xiaohui Tian; Wei Yang; Liying Zhao; Yiguang Lu; Xiang Li; Ao Cheng; Shu Liu; et al. (Environmental Research, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Insights into the enhanced flux and robust desalination of hydrogel composite Janus membrane in membrane distillation: overlooked interfacial compatibility - Shu Jiang; Anqi Luo; Shilei Fu; Yanrui Wang; Kexin Hou; Jun Ma; Longfeng Hu; Nuo Cheng; Xiaobin Tang; Heng Liang (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Amitriptyline toxicity mechanisms in Chlorella vulgaris and potential for bioremediation of contaminated wastewater - Wenjie Yuan; Yicheng Wu; Yeling Zhou; Bingjun Shu; Jinqi Cai; Haiyan Fu (Algal Research, 2026)

Analyzing maize stem circumference, stem height, and stem circumference-to-height ratio using UAV, UGV, and deep learning - Jianing Shen; Jibo Yue; Yang Liu; Yihan Yao; Haikuan Feng; Hao Yang; Wei Guo; Xinming Ma; Yuanyuan Fu; Meiyan Shu; Guijun Yang; Hongbo Qiao (Computers and Electronics in Agriculture, 2025)

Susceptibility of five thrips pests to spinetoram and the frequency of G275E target-site mutation in a major vegetable production region of China - Hong-Ping Tian; Hong-Xia Tian; Jin-Cui Chen; Fu-Jun Li; Jing-Jing Kang; Hui-Juan Li; Jin-Peng Gao; Guo-Cai Lu; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

10-Hydroxy-2-decenoic acid ameliorates LPS-induced acute lung injury through targeting MD2-mediated inflammatory signaling pathways - Cong Shu; Chen Li; Huamin Liu; Zengxian Zhou; Chenghao Qian; Zhuohui Xie; Fenfen Lin; Yuxiao Jiang; Ruping Chen; Yue Liu; Xin Liu; Gaozhi Chen; et al. (Toxicology and Applied Pharmacology, 2025)

3D reconstruction of pore throat connectivity in Shale: An SAXS-MICP integrated framework - Linhao Zhang; Shu Jiang; Jiale Fu; Fei Xie; Zhile Han; Zihao Li; Mengdi Sun (Marine and Petroleum Geology, 2025)

A framework for ecological restoration baseline delineation integrating geology-landscape-ecology and carbon sinks based on geographical similarity - Shu Wang; Quanli Xu; Shengfeng Li; Zhaoxin Fu; Yijing Lin (Journal of Environmental Management, 2025)

Dynamic regulation of mung bean globulin amyloid fibrillation by Gallic acid: Structural and functional insights - Peng Jiang; Qingpeng Xu; Shu Zhang; Tianxin Fu; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Research International, 2025)

Multigraph fusion neural network for predicting available cadmium levels in farmland soils - Ren-Jie Zhang; Shu-Fang Pan; Huai-Zeng Xing; Tian-Hao Dong; Sai-Hua Liu; Tao Xue; Fa-Xiang Tian; Hong-Yu Fu; Yun-He Xie; Xiong-Hui Ji (Environmental Pollution, 2025)

An Improved Fractional Damage Creep Model for Shale and Its Application to the Long-term Fracture Conductivity Prediction - Jiale Fu; Shu Jiang; Linhao Zhang; Pengfei Xiong; Kai Zhang (Computers and Geotechnics, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

An investigation of localized entropy driven cathode electrolyte interphase to a one-step complete deprotonation of ethylene carbonate on Ni-rich layered material of lithium-ion battery - Laurien Merinda; Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Chusnul Khotimah; Han-Pin Hsieh; Jeng-Kuei Chang; Shu-Chih Haw; Chih-Wen Pao; Jeng-Lung Chen; Qunjie Xu; et al. (Chemical Engineering Journal, 2025)

Lactobacillus delbrueckii Alleviate Oxidative Stress and Intestinal Injuries by Activating TLR2 and TLR4 Expressions in IPEC-J2 Cells - Fengming Chen; Shu Wu; Xiaoyu Wang; Yinghui Li; Binsheng He; Yafen Fu; Xingguo Huang; Jiayi Chen (Probiotics and Antimicrobial Proteins, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Efficient socket-based data transmission method and implementation in deep learning - Xin-Jian Wei; Shu-Ping Li; Wu-Yang Yang; Xiang-Yang Zhang; Hai-Shan Li; Xin Xu; Nan Wang; Zhanbao Fu (Applied Geophysics, 2025)

Late Cenozoic Climates and Mountains Drove Diversification of the Pardosa laura Species Complex From Eastern China - Li‐Juan Liu; Dan Fu; Shu‐Qiang Li; Yu‐Fa Luo (Journal of Biogeography, 2025)
Aim To test how evolutionary processes of spiders in mountain ranges of eastern China were in response to environmental changes, we analyze the correlation between diversification of the Pardosa laura species complex (Araneae, Lycosidae) and historical climates and mountains in this region. Methods We reconstruct phylogenetic relationships and patterns of phylogeography and genetic diversity using mtDNA data from samples spanning the full range of the species complex P. laura in eastern China. Results The P. laura species complex clustered into four lineages: Lineage I includes five haplotypes from the areas to the north of the Yinshan‐Yanshan Mountains; Lineage II consists of 23 haplotypes from the areas between the Qinling Mountains–Huaihe River Line and the Nanling Mountains; Lineage III and IV are composed of 21 and 62 haplotypes, respectively, from the areas between the Yinshan‐Yanshan Mountains and the Nanling Mountains. Each lineage corresponds to that, grouped from haplotype network analyses, with the same geographic distribution areas. All four lineages initially diversified during about 1.43 and 0.24 Ma ago (Ma) in relation to the Pleistocene glacial‐inglacial cycles. The biogeographic reconstructions suggest that the species complex P. laura most likely originated in central China around 7.68 (11.17–4.85) Ma in relation to the recent ( approximately 8 Ma) expansion of grasslands and retraction of forests. The inter‐colony dispersal between central China and northeastern China occurred during the late Neogene, between around 7.68 and 3.14 Ma. Central China is an important dispersal center, with dispersal to southwestern and northern China between the late Pliocene and middle Pleistocene, approximately 3.14–2.89 and 2.89–1.43 Ma, respectively. Main Conclusions The contemporary genetic structure of the P. laura species complex presents a high correlation between lineages and geographic distribution. The historical phylogeographic patterns suggested that the late Cenozoic climate changes and the mountainous corridors and isolation events, as well as the lineage dispersals and ecological adaptations shaped the diversification of a spider species complex in eastern China over long timescales.

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

The impact of China's Clean Air Action and future strategies: Actions targeting regionally dominant sources - Xuelian Peng; Nan Fu; Jinze Wang; Yuanchen Chen; Kang Mao; Lu Zhang; Yiming Qin; Jianhuai Ye; Wei Du; Peng Zhang; Bo Pan; Shu Tao (Journal of Environmental Management, 2025)

A novel fully coupled thermal-hydraulic-mechanical model for hydrogen storage in depleted gas reservoirs - Jing Fu; Keni Zhang; Hongjun Yin; Philip H. Winterfeld; Yu-Shu Wu (Gas Science and Engineering, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Thermally conductive and hygroscopic poly(acrylamide-dimethylacrylamide) double-network hydrogel for effective heat dissipation - Shu Geng; Pingyang Sun; Linguangze Zhuo; Xiaojing Hao; Shuai He; Erjiang Fu; Cyrille Boyer; Jin Zhang (Chemical Engineering Journal, 2025)

A nine-year statistical study on the thunderstorms generated amid Dabie vortex background - Xue Xiao; Shen-Ming Fu; Bo Wang; Chao-Ying Yang; Shu-Guang Ning; Shi-Jun Sun; Kun-Shuang Zhu; Jian-Hua Sun (Atmospheric Research, 2025)

Does the cropping system have a substantial influence on greenhouse gas emissions? Dynamics and key factors-based insights from an empirical study of China - Jiongxin Chen; Jianjun Zhang; Shu Fu; Sen Liang; Ke Wang (Agricultural and Forest Meteorology, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Environmental variables affect the effectiveness of ecosystem services of ecological restoration project: Evidence from Xiangjiang River Basin-Dongting Lake - Shu Fu; Jianjun Zhang; Yufei Li; Wei Chen; Yaping Zhang; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2025)

Intrinsic electron transfer kinetics of electroactive granular sludge bioanode boosting bio-electro-Fenton efficiency - Bao-Gang Fu; Shu-Na Li; Xiangtong Zhou; Xiang Xiao; Liang Cheng; Yang-Yang Yu (Journal of Environmental Chemical Engineering, 2025)

Volatile-char interactions during biomass pyrolysis: Effect of decoupled primary and secondary interactions on product control - Anjiang Gao; Hekuan Fu; Weiwei Wu; Shihao Lv; Wenran Gao; Nanfeng Zhu; Yong Huang; Félix Mérimé Bkangmo Kontchouo; Shu Zhang (Fuel, 2025)

Integrating and mapping spatial heterogeneity of the ecosystem: a novel approach to indicating environmental threats - Xiaojie Wei; Yanan Zhang; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu (Environmental Research, 2025)

Biphasic continuously composite electrolyte design for high-performance solid-state Li–CO2 batteries - Qian-Cheng Zhu; Shu-Jian Li; Zi-Yuan Wang; Fu-Li Zhang; Jin-Hao Xie; De-Yu Mao (Chemical Engineering Journal, 2025)

Improving microbial degumming efficiency for ramie fibers: Synergistic action of enhanced xylanase activity and optimized pretreatment - Tong Shu; Pandeng Li; Ziqi Hou; Huihui Wang; Tianyi Yu; Yulong Chen; Chunhua Fu; Longjiang Yu (Bioresource Technology, 2025)

Identification and interaction mechanism of novel small molecule antagonists targeting CC chemokine receptor 1/3/5 for treatment of non-small cell lung cancer - Xiaomeng Wang; Juan Wang; Qiao Fu; Jing Luo; Mao Shu; Zhihua Lin (Molecular Diversity, 2025)

A Machine Learning with Ordinal Ranking Approach for Dysarthria Severity Classification in Parkinson’s Disease - Fu-Yu Beverly Chen; Chung-Yao Chien; Kuel-Fu Yu; Shu-Wei Tsai (Journal of Medical and Biological Engineering, 2025)

Sublethal deltamethrin induces transgenerational fitness costs in Neoseiulus agrestis (Karg) (Acari: Phytoseiidae): impaired parental reproduction and offspring development - Jing Chang; Shu-Lei Zhang; Cheng Wang; Xiao-Tong Fu; Zhi-Jia Huo; Rui-Xia Meng (Experimental and Applied Acarology, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Immune responses of Ctenopharyngodon idella juveniles against the ciliated parasite's reinfection induced by Ichthyophthirius multifiliis theronts at the threshold density - Ting-Long Hou; Yao-Wu Fu; Xing-Chi Guo; Shu-Guan Guo; Shi-Lu Huang; Qi-Zhong Zhang (Aquaculture, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Constructing WO3/g-C3N4/BiOBr as efficient dual Z-scheme heterojunction nanocomposite for LED light-driven inactivation of bacteria - Yanyan Fu; Shuangxiu Shu; Jun Huang; Wenhui Bian; Lijing Huang; Liying Huang; Yeping Li (Journal of Water Process Engineering, 2025)

Effectiveness of governmental and policy initiatives in reducing agricultural greenhouse gas emissions: An empirical analysis of West Africa - Iskid Jacquet; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu; Shidong Liu (Environmental Development, 2025)

Multi-omic profiling reveals green manuring with maize enhances fruit quality of strawberry via the microbiome–plant–metabolite axis - Huijing Fu; Chenyu Sun; Xiaolong Shu; Meilin Zhang; Zirong Kong; Fan Qi; Quanhong Xue; Hangxian Lai; Qiao Guo (Plant and Soil, 2025)

Integrated LC-MS/MS, Network Pharmacology, and Experimental Validation Reveal the Mechanism of Eucommia Ulmoides against Osteoarthritis - Danqing Fu; Chun Gan; Shiyu Gao; Jialu Shu; Shenman Zhou; Ke Zhou; Zhenyan Peng; Haoqiang Dai; Chenjie Xia (Cell Biochemistry and Biophysics, 2025)

Isolation of a new natural bromopyrrole alkaloid agenakasine, a biosynthetically related metabolite laughine, and norzooanemonin from a marine sponge Agelas nakamurai - Chung-Wei Fu; Atallah F. Ahmed; Lin Chiang; Shu-Fen Chiou; Hui-Chun Wang; Jyh-Horng Sheu (Phytochemistry Letters, 2025)

Role of macrophage ATP metabolism disorder in SiO2‑induced pulmonary fibrosis: a review - Hui-jie Hu; Yuan-yuan Fu; Shu-ling Du; Yu-han Zhang; Zhao-qiang Zhang; Gui-zhi Han (Purinergic Signalling, 2025)

Biodegradable Mg–Cu alloy inhibits HBV replication and hepatocellular carcinoma progression - Heyu Zheng; Weiping Zhou; Meiqi Mao; Yiwei Wang; Xing Tian; Biao Yang; Lu Zhao; Shu Li; Ye Sun; Zhongjia Jiang; Ronghua Fan; Yuxin Bai; et al. (BioMetals, 2025)

Highly sensitive, anti-freezing and stretchable hydrogels with modified MXene for multifunctional applications - Xiang-Shu Hu; Xin Jing; Jing-Wen Mei; Fu-Xiang Liu; Pei-Yong Feng; Jiayi Xu; Yue-Jun Liu (Food Chemistry, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Stabilization of Copper, Lead, and Zinc in Copper Smelting Slag Tailings by Sulfate-reducing Bacteria Using Typical Industrial By-product Gypsum as a Sulfur Source - Wei Zhang; Kaibin Fu; Shu Chen; Qian Zhou; Leming Zhu; Jun Yao (Water, Air, & Soil Pollution, 2025)

Chitosan Nano-Selenium Supplementation Improves Production Performance, Egg Quality, and Selenium Deposition in Aging Laying Hens - Gang Shu; Xin Yi; Lei Yang; Jingyi Chen; Kang Fu; Haohuan Li; Funeng Xu; Wei Zhang; Hualing Fu; Bo Jing; Felix Kwame Amevor; Yingjie Wang; et al. (Biological Trace Element Research, 2025)

Response of ecological condition in ecologically fragile areas to disturbance from extreme precipitation event: An empirical analysis from the loess plateau - Kexin Yi; Jianjun Zhang; Haoyi Lei; Wei Chen; Yaping Zhang; Shu Fu; Ke Wang (Journal of Cleaner Production, 2025)

Chemical composition, antioxidant activity, α-glucosidase inhibitory activity, and metabolomic profiling of Dendrobium officinale across diverse growing regions and cultivation modes - Shu He; Zhengli Lu; Rurui Li; Chun Chen; Xiong Fu; Kin Weng Kong; Amin Ismail; Xuechun Zhang; Zhenxing Wang (Food Bioscience, 2025)

Accumulation of microtubule-associated protein tau promotes hepatocellular carcinogenesis through inhibiting autophagosome-lysosome fusion - Xuemin Liu; Zhiwei Hao; Huanhuan He; Xuan Wang; Wenqi Wang; Xiji Shu; Binlian Sun; Zhiyong Hu; Shaobo Hu; Xiaoying Hou; Yue Xiao; Hongyan Zhou; et al. (Molecular and Cellular Biochemistry, 2025)

Deciphering the effective substances of mangrove plant Acanthus ilicifolius Linn. against liver injury - Qing Zhao; Shu-Yue Song; Han Fang; Yao-Yao Zheng; Meng-Qi Zhang; Xia Ren; Ya-Hui Zhang; Xiu-Mei Fu; Xin Li; Chang-Yun Wang (Natural Product Research, 2025)

Remotely estimate the cropland fractional vegetation cover using linear spectral mixture analysis and improved band operations - Yihan Yao; Jianing Shen; Jibo Yue; Yang Liu; Haikuan Feng; Meiyan Shu; Yuanyuan Fu; Hongbo Qiao; Tong Sun; Guang Zheng (International Journal of Remote Sensing, 2025)

Hydrogen production by suspension self-rotation enhanced pyrolysis of sludge particles in cyclone - Zhiqin Jiang; Yanan Liang; Shu Zhu; Kai Zheng; Yingjie Zhu; Danhui Yang; Hualin Wang; Pengbo Fu (Water Research, 2025)

Ammonia and amines emissions from residential biomass combustion in China from 2014 to 2030 - Wei Du; Su Jiang; Nan Fu; Jialuo Song; Xianbiao Lin; Kang Mao; Jianwu Shi; Yuanchen Chen; Jiangping Liu; Shu Tao (Journal of Hazardous Materials, 2025)

Ambient-temperature α-pinene hydrogenation to cis-pinane over Ru/CeO2-H catalyst via the dimethyl-up configuration - Yu-Xuan Fu; Shu-Yi Huang; Ming-Shuai Sun; Yan Zhou; Dan-Dan Cai; Wen-Shuai Zhu; Wei Hui; Duan-Jian Tao (Chemical Engineering Journal, 2025)

Improving resilience to extreme heat events through green space morphology: A threshold-based perspective - Yixin Dai; Jianjun Zhang; Shu Fu; Wei Chen; Yaping Zhang; Kexin Yi (Sustainable Cities and Society, 2025)

Numerical study on wave–wind coupling effects on hydrodynamics and light capture performance of offshore multi-body floating photovoltaic system - Jia Fu; Yun-Peng Zhao; Guang-Chen Jia; Chao Ma; Jia-Qing Shu; Yan-Qian Sun (Ocean Engineering, 2025)

Potential function of plant-growth-promoting endophytic Serratia fonticola CPSE11 from Codonopsis pilosula in phytoremediation of Cadmium ion (Cd2+) - Mingjun Yang; Yunxing Fu; Shu Hu; Feifan Leng; Yan Zhuang; Wenbin Sun; Yonggang Wang (Journal of Environmental Management, 2025)

Soil and litter microbiomes as joint drivers of ecosystem multifunctionality in a 60-year-old forest plantation - Shu-Yi-Dan Zhou; Xu Li; Josep Peñuelas; David T. Tissue; Roy Neilson; Xujun Liu; Zhiyang Lie; Fu-Yi Huang; Junhua Yan; Dong Zhu; Juxiu Liu (Journal of Environmental Management, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Taxonomic, phylogenetic, and functional β-diversity along an urbanization gradient in Taipei metropolitan area - Shu-Wei Fu; Jerome Chie-Jen Ko; Tzung-Su Ding (Urban Ecosystems, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

How landscape characteristics impact land surface temperature in the context of urban spatial heterogeneity: A case study from Beijing, China - Wei Chen; Jianjun Zhang; Chenyan Huang; Shu Fu (Urban Climate, 2025)

Measuring heat transfer index (HTI): A new method to quantify the spatial influence of land surface temperature between adjacent urban spaces - Wei Chen; Jianjun Zhang; Chenyan Huang; Shu Fu; Sen Liang; Ke Wang (Sustainable Cities and Society, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Effect of oral Mn-based nanozymes Mn3O4 NPs on morphological, antioxidation, mucosa, and fecal microbial community in mice colons - Baoyue Zhang; Lei Yang; Zhengkun Wu; Xianxiang Wang; Xiaoling Zhao; Wei Zhang; Danqin Li; Hualin Fu; Juchun Lin; Funeng Xu; Xiaoyang Ai; Gang Shu (Food and Chemical Toxicology, 2025)

Determining representative elementary volume for hydraulic conductivity of fractured rock masses: Comparative analytical and numerical studies - Tai-Sheng Liou; Jia-Jing Lin; Po-Kai Chen; En-Chao Yeh; Fu-Shu Jeng; Tai-Tien Wang (Engineering Geology, 2025)

In-situ gel injection of poloxamer-based metamizole provides long-acting antipyretic effects - Yueli Wang; Dongbo Li; Xiaojuan Li; Dandan Ren; Wei Zhang; Gang Shu; Juchun Lin; Haohuan Li; Funeng Xu; Guangneng Peng; Hualin Fu (Drug Delivery and Translational Research, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Establishment and application of TaqMan probe-based quantitative real-time PCR for rapid detection and quantification of Ichthyophthirius multifiliis in farming environments and fish tissues - Shu-Quan Guo; Yao-Wu Fu; Ting-Long Hou; Shi-Lu Huang; Qi-Zhong Zhang (Veterinary Parasitology, 2025)

The interplay of singlet oxygen and ABI4 in plant growth regulation - Zhong-Wei Zhang; Yu-Fan Fu; Guang-Deng Chen; Christiane Reinbothe; Steffen Reinbothe; Shu Yuan (Trends in Plant Science, 2025)

The induction of polyamines metabolism pathway and membrane stability with silicon alleviate the vanadium toxicity in pepper plants - Naveed Mushtaq; Muhammad Ahsan Altaf; Huangying Shu; Xu Lu; Shanhan Cheng; Mohamed A. El-Sheikh; Parvaiz Ahmad; Huizhen Fu; Zhiwei Wang (Journal of Hazardous Materials, 2025)

Coal dust combustion suppression via melamine polyphosphate and silica: Experiment and simulation - Shuang Geng; Ting Zhang; Xin Zhang; Shaoqian Cheng; Guoen Fu; Jianfu Xu; Wen Zhou; Yanhua Lan; Xueqiang Shi; Chi-Min Shu; Weiguo Cao (Fuel, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Transient cooling performance and parametric characteristic of active–passive coupling cooling system integrated air-conditioner, PV-PCM envelope, and ice storage - Ying-Xi Huang; Zheng-Yu Shu; Zi-Quan Liu; Yang Cai; Wei-Wei Wang; Fu-Yun Zhao (Energy and Buildings, 2025)

Topology of gut Microbiota Network and Guild-Based Analysis in Chinese Adults - Jiongxing Fu; Danxia Yu; Wei Zheng; Yu Jiang; Lei Wang; Hui Cai; Qinghua Xia; Xiao-Ou Shu; Wanghong Xu (Phenomics, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Design of Ni-based heterostructured catalyst with Ni3+ for enhanced bidirectional sulfur conversion - Yurui Wu; Wei Li; Hengzhi Liu; Yufang Chen; Manfang Chen; Xingqiao Wu; Yunfeng Peng; Wenlong Xia; Yuchao Du; Keyang Fu; Xiukang Yang; Xianyou Wang; et al. (Chemical Engineering Journal, 2025)

Contrasting molecular structures and photooxidation behaviors between dissolved organic sulfur released from rice straw-biochar and aerobically decomposed rice straw - Chenhui Wei; Heyun Fu; Xiaolei Qu; Shu Tao; Patrick G. Hatcher; Dongqiang Zhu (Chemical Geology, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

Atmospheric deposition of pollutants at three altitudes on Mount Emei, Sichuan Basin, southwestern China - Zhongjun Xu; Yuhan Fu; Qi Ying; Philip K. Hopke; Xi Shu; Xiaolan Yang; Xue Qiao; Ya Tang (Science of The Total Environment, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

Three-dimensional porous Ti supported Ni/Sb Co-doped SnO2 anode for electrocatalytic production of ozone - Mengqing Hu; Di Zhao; Mengyang Dong; Huai Qin Fu; Yu Zou; Yiming Xu; Ming Zhou; Lei Zhang; Liang Wang; Yajie Shu; Kaidi Zhang; Ziyao Chen; et al. (Journal of Environmental Chemical Engineering, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Vertical distribution of aerosols and association with atmospheric boundary layer structures during regional aerosol transport over central China - Xiaoyun Sun; Yue Zhou; Tianliang Zhao; Weikang Fu; Zhuang Wang; Chune Shi; Hao Zhang; Yuqing Zhang; Qingjian Yang; Zhuozhi Shu (Environmental Pollution, 2024)

Atmospheric Sulfur and Nitrogen Deposition in Five Nature Reserves of Sichuan Basin to Qinghai-Tibetan Plateau Transect Region, Southwestern China - Zhongjun Xu; Xi Shu; Han Yang; Liqiang Fu; Tingting Liu; Zhonglin Xia; Xue Qiao; Ya Tang (Chinese Geographical Science, 2024)

Folding of a single layer in an anisotropic viscous matrix under layer-parallel shortening - Yuan-bang Hu; Paul D. Bons; Tamara de Riese; Shu-gen Liu; Maria-Gema Llorens; Eloi González-Esvertit; Enrique Gomez-Rivas; Dian Li; Yu-zhen Fu; Xue-lin Cai (Journal of Structural Geology, 2024)

Comprehensive evaluation of the distribution, transport and ecological risk of heavy metals in intra-urban river sediments using high-resolution techniques - Kang Liao; Weijie Li; Zhiwei Huang; Shu Lin; Lingfang Fu; Wei Liu; Huaiyang Fang; Hong Deng (Environmental Pollution, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Evaluation of the Regulation and Response of Ocean Heat Content to Typhoons in the Northwest Pacific Based on GDCSM_Argo - Han Su; Chunling Zhang; Bo Shu; Lifu Fu (Journal of Marine Science and Engineering, 2024)
The Northwest Pacific is a source of strong typhoons accompanied by significantly changing ocean heat content (OHC). Based on the GDCSM_Argo dataset, all typhoons within twenty years are considered to explore the regulation of OHC between 0 and 2000 m with typhoons in this study. The results show a weak correlation between OHC and typhoons but a strong correlation between ocean heat content uptake anomaly (OHUA) and typhoons by wavelet, lag/lead, and EOF analyses. The energy reserve effect by the OHUA on typhoon generation is most significant at a 3-month lag. The OHUA above 300 m primarily influences typhoons’ temporal and spatial characteristics. On the other hand, typhoons enhance vertical transmission of OHC through entrainment. A modified version of the Richardson number (Rohc) is used for the characterization of the hydrostatic stability between ocean layers. The entrainment is particularly strong in the Northwest Pacific north of 20° N, where Rohc is between −0.2 and 0. The OHC below the mixed layer also responds to typhoon disturbances but transports less heat vertically than the near-surface layers. Our results suggest that GDCSM_Argo provides reliable data support for the study of the relationship between OHC and typhoons.

Aflatoxin B1 as a complicit in intestinal damage caused by Eimeria ovinoidalis in lambs: Novel insights to reveal parasite-gut battle - Pan Chen; Wen-li Ding; Bo-wen Xu; Mujeeb Ur Rehman; Kai-li Liu; Yan-feng He; Sen-yang Li; Fu-chun Jian; Shu-cheng(淑成) Huang(黄) (Science of The Total Environment, 2024)

Heating pattern and effects of built-up land in response to influencing factors: A statistical estimation of 172 Chinese cities - Wei Chen; Jianjun Zhang; Yaping Zhang; Shu Fu; Kexin Yi; Yixin Dai (Journal of Cleaner Production, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

Waste milk-derived biodegradable mulch film fabrication and nutrient slow-release performance evaluation - Yanping Zhu; Bingbing Fu; Pengjin Zhu; Shihu Shu; Dongfang Wang; He Xu; Dongqing Cai (Chemical Engineering Journal, 2024)

Bayesian inversion of HFC-134a emissions in southern China from a new AGAGE site: Results from an observing system simulation experiment - Juan Li; Jianxiong Sheng; Lei Zhu; Bo Yao; Jing Wu; Dongchuan Pu; Lei Shu; Song Liu; Xicheng Li; Yuyang Chen; Xiaoxing Zuo; Yali Li; et al. (Atmospheric Environment, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Engineering the nanozyme hydrogel beads by polyvinyl alcohol/chitosan encapsulation with recyclable and sustainable catalytic activity for visual analysis of hydrogen peroxide - Chonghui Wei; Shu Zhu; Jiacheng Lu; Aoran Guan; Yan Sun; Liyun Zeng; Jinghao Fu; Xingyu Luo (Analytica Chimica Acta, 2024)

Ozone pollution aggravated by mountain-valley breeze over the western Sichuan Basin, Southwest China - Yuqing Zhang; Tianliang Zhao; Xiaoyun Sun; Yongqing Bai; Zhuozhi Shu; Weikang Fu; Zhen Lu; Xinyue Wang (Chemosphere, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Cevanine-type steroidal alkaloids from the bulbs of Fritillaria cirrhosa D. Don - Hui-wen Dong; Shu-hui Wang; Tse Wai Ming; Shao-bing Fu; Yun-hu Zhang; Jia-wei Li; Qing-ying Zhang; Peng-fei Tu; Hong Liang (Phytochemistry, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Ectopic expression of OsWOX9A alters leaf anatomy and plant architecture in rice - Dandan Li; Longjiang Fan; Qingyao Shu; Fu Guo (Planta, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Combining canopy spectral reflectance and RGB images to estimate leaf chlorophyll content and grain yield in rice - Zhonglin Wang; Xianming Tan; Yangming Ma; Tao Liu; Limei He; Feng Yang; Chuanhai Shu; Leilei Li; Hao Fu; Biao Li; Yongjian Sun; Zhiyuan Yang; et al. (Computers and Electronics in Agriculture, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Bicyclol mitigates lipopolysaccharide-induced acute lung injury through myeloid differentiation factor 88 inhibition - Lili Fu; Linting Cheng; Junliang Lu; Qianru Ye; Cong Shu; Chuchu Sun; Zhiguo Liu; Guang Liang; Weixin Zhao (Toxicology and Applied Pharmacology, 2024)

Moisture Sources and Transport Paths during the Summer Heavy Rainfall Events in the Three-River-Headwater Region of the Tibetan Plateau - Shujing Shen; Hui Xiao; Huiling Yang; Danhong Fu; Weixi Shu (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Biocompatible porous material templated from gliadin particle and gellan gum co-stabilized wet foam - Fu-Zhen Zhou; Tao Yang; Huan Xiang; Long-Tao Zhang; Shu-Heng Wei; Jian-Hua Zhu; Xiao-Quan Yang; Shou-Wei Yin (Food Hydrocolloids, 2024)

Synthesis of high-performance low-Pt (1 1 1)-loading catalysts for ORR by interaction between solution and nonthermal plasma - Shuxiu Yang; Qingzhu Shu; Bona Fu; Shuhong Liu; Yong Zhang; Hong Zhao (Chemical Engineering Journal, 2024)

Enhanced Removal of Antimony and Aniline from Wastewater by Combining Electrocoagulation with Peroxymonosulfate - Wenjie Dong; Yu Shu; Ao Cai; Jiazhi Wang; Zhixi Dai; Beimeng Qi; Hailu Fu (Water, Air, & Soil Pollution, 2024)

Biogeochemical processes in heterogeneous soil-Solanum nigrum L. system control lead partitioning: Roles of strengite and oxalated zero-valent iron nanoparticle - Guoqing Dai; Hao Shi; Murray B. McBride; Haojie Fu; Zheng Li; Xinlei Wang; Shu Yang; Lei Wang; Fayuan Wang; Xinxin Li (Journal of Cleaner Production, 2024)

Exogenous strigolactone enhanced the drought tolerance of pepper (Capsicum chinense) by mitigating oxidative damage and altering the antioxidant mechanism - Huangying Shu; Kaijing Xu; Xiangrui Li; Jiancheng Liu; Muhammad Ahsan Altaf; Huizhen Fu; Xu Lu; Shanhan Cheng; Zhiwei Wang (Plant Cell Reports, 2024)

Polycyclic aromatic compounds (PACs) in industrial soils from northwestern of China: occurrence, distribution, exposure risk, and implications on risk-based controls - Yousong Zhou; Kai Xiao; Yongqiang Zhang; Donglei Fu; Ke Jiang; Jinmu Luo; Yuancheng Li; Guofeng Shen; Wenxin Liu; Shu Tao; Senlin Lu (Environmental Geochemistry and Health, 2024)

Secondary inorganic aerosols and aerosol acidity at different PM2.5 pollution levels during winter haze episodes in the Sichuan Basin, China - Xiaoxin Fu; Xinming Wang; Tengyu Liu; Quanfu He; Zhou Zhang; Yanli Zhang; Wei Song; Qunwei Dai; Shu Chen; Faqin Dong (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Holocene temperature and cold events recorded in arid Central Asian peatlands - Haiyan Zhao; Weijian Zhou; Peng Cheng; Xuefeng Yu; Yubin Wu; Peixian Shu; Feng Xian; Hua Du; Jie Zhou; Guoqing Zhao; Yukun Fan; Yunchong Fu; et al. (Quaternary Science Reviews, 2024)

Mapping the profiles and underlying driving mechanisms of the antibiotic resistome and microbiome within a subtropical complex river watershed - Xin-Yuan Zhou; Shu-Yi-Dan Zhou; Fu-Yi Huang; Longji Zhu; Jian-Qiang Su (Journal of Hazardous Materials, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Identification and characterization of β3 integrin in Crassostrea hongkongensis - Lei Tang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Thermal degradation kinetics of cynatratoside-C and its antiparasitic efficacy after being stored in sterile water and aquaculture water - Shi-Lu Huang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Accident case data-accident causation model driven safety training method: Targeted safety training empowered by historical accident data in coal industry - Xie Xuecai; Fu Gui; Shen Shifei; Shu Xueming; Li Jing; Huang Lida; Wei Na (Process Safety and Environmental Protection, 2024)

Long-term seawall barriers lead to the formation of an urban coastal lagoon with increased antibiotic resistome - Shu-Yi-Dan Zhou; Kai Yang; Roy Neilson; Hu Li; Hong-Zhe Li; Yan-Yan Zhou; Juxiu Liu; Jian-Qiang Su; Fu-Yi Huang (Journal of Environmental Management, 2024)

Eliminating concentration polarization with gradient lithiophilic sites towards high performance lithium metal anodes under low N/P ratio - Zichun Xiao; Duzhao Han; Yu Fu; Keyu Xie; Wensheng Tian; Chengyong Shu; Kai Xi; Chengxin Peng; Yuping Wu; Shixue Dou; Wei Tang (Chemical Engineering Journal, 2024)

A more accurate estimation with kernel machine for nonparametric spatial lag models - Yu Shu; Jinwen Liang; Yaohua Rong; Zhenzhen Fu; Yi Yang (Spatial Statistics, 2023)

Exploring spatial-temporal driving factors for changes in multiple ecosystem services and their relationships in West Liao River Basin, China - Wei Jiang; Bojie Fu; Guangyao Gao; Yihe Lv; Cong Wang; Siqi Sun; Kai Wang; Stefan Schüler; Zhongguo Shu (Science of The Total Environment, 2023)

Classification of five SARS-CoV-2 serotypes based on RBD antigenicities - Shixiong Hu; Chunli Wu; Xinkai Wu; Xuehui Ma; Chang Shu; Qian Chen; Anqi Zheng; Huiting Yang; Jian Lu; Pei Du; George Fu Gao; Qihui Wang (Science Bulletin, 2023)

Application of engineered heme enzymes based on myoglobin with high peroxidase activity for efficient degradation of various emerging pollutants - Guang-Rong Wu; Jia-Kun Xu; Li-Juan Sun; Ying-Fu Li; Shu-Qin Gao; Ying-Wu Lin (Journal of Environmental Chemical Engineering, 2023)

Toward a sound understanding of a large-scale landslide at a mine waste dump, Anshan, China - Shu-wei Sun; Liu Liu; Zhao-xi Yang; Xin-yu Fu (Landslides, 2023)

Mitigating greenhouse gas emissions from agriculture in Benin: spatial estimation and reduction options - Iskid Jacquet; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu; Shidong Liu (Environment, Development and Sustainability, 2023)

Distinct patterns of the soil and phyllosphere antibiotic resistome in natural forest ecosystems under an altitudinal gradient - Shu-Yi-Dan Zhou; Fu-Yi Huang; Wei Su; Zhiyang Lie; Yue Liu; Chenshuo Lin; Kai Yang; Ze Meng; Zhanfeng Liu; Roy Neilson; Jian-Qiang Su; Juxiu Liu (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

The strength characteristics and competitive failure mechanism of primary coal-rock combination considering interface damage quantity - Kai Wang; Qiang Fu; Chao Xu; Zibo Ai; Dan Li; Longyong Shu (Fuel, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Monitoring performance of slopes via ambient seismic noise recordings: Case study in a colluvium deposit - Zhen Guo; Mi Zhou; Yu Huang; Jian Pu; Shu Zhou; Boyu Fu; Adnan Aydin (Engineering Geology, 2023)

Cloud Microphysical Processes and Atmospheric Water Budget during the 20 July 2021 Extreme Precipitation Event in Zhengzhou, China - Weixi Shu; Danhong Fu; Hui Xiao; Huiling Yang; Yue Sun; Xueliang Guo; Yang Zhao; Jianfang Ding; Shujing Shen (Journal of Meteorological Research, 2023)

Bisphenol P and bisphenol M promote triple-negative breast cancer metastasis through activation of AKT pathways - Jinmi Liu; Haiping Wang; Xiaoying Hou; Limei Fan; Fang Yang; Yuhang Dai; Yufei Deng; Zhengqi Fu; Xiji Shu; Binlian Sun; Yuchen Liu (Science of The Total Environment, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Distribution, sources, and ecological risk assessment of polycyclic aromatic hydrocarbons in sediments from Baiyang Lake, China - Liguo Fu; Yaxue Sun; Hongbo Li; Yan Chen; Hui Du; Shu-xuan Liang (Environmental Monitoring and Assessment, 2023)

Developing and characterizing monoclonal antibodies of Guertu bandavirus nucleoprotein for developing methods of Guertu bandavirus and severe fever with thrombocytopenia syndrome virus detection - Jin Qian; Liyan Fu; Xiaoli Wu; Zhiying Wang; Hualin Wang; Yan Zeng; Guirong Cheng; Fei Deng; Shu Shen (Brazilian Journal of Microbiology, 2023)

Bilateral fluctuation asymmetry of otoliths of Collichthys lucidus in different functional areas of Haizhou Bay - Shike Gao; Xiao Zhang; Ruilin Shu; Shuo Zhang; Jikun Lu; Guanghui Fu (Journal of Fish Biology, 2023)
The fluctuating asymmetry (FA) of fish otoliths can reflect the difference in the growth and development of fish in sea areas greatly affected by environmental pressure, thus enabling the assessment of different habitats. In this study, using 113 Collichthys lucidus samples collected from different functional areas (estuary area, aquaculture area, artificial reef area and natural area) in Haizhou Bay, the square coefficient of asymmetry variation ( CV 2 a ) of four characters (length, width, perimeter and area) of the left and right sagittal otoliths was calculated. The results showed that the CV 2 a value of otolith width was the lowest and that of otolith length was the highest. The CV 2 a value had no obvious regularity with increasing fish body length. In addition, the CV 2 a values of the four characteristics reached their lowest values in the artificial reef area, indicating that the construction of marine ranching dominated by artificial reefs may partly improve the aquatic environment in this functional area. We consider that the otolith FA of C. lucidus can be used as a characteristic of environmental stress between different areas/regions/habitats.

Early-Middle Devonian adakitic magmatism generated by slab retreat in southern West Junggar, NW China: implications for tectonic correlation with central and East Kazakhstan - Rong Ren; Bo Liu; Bao-Fu Han; Shu-Wei Guan (International Geology Review, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

3D-printed stretchable sensor based on double network PHI/PEDOT:PSS hydrogel annealed with cosolvent of H2O and DMSO - Xiu-Yan Cheng; Shu-Qiang Peng; Li-Xin Wu; Qing-fu Sun (Chemical Engineering Journal, 2023)

Effects of the multi-stress-resistant strain Zygosaccharomyces parabailii MC-5K3 bioaugmentation on microbial communities and metabolomics in tobacco waste extract - Ming Shu; Yang Yang; Fanda Pan; Tengfei Bian; Qi Li; Fu Liao; Wenmiao He; Shitou Li; Jian Xu; Tong Hu; Pei Qiao; Weihong Zhong (Archives of Microbiology, 2023)

Long-term hypoxia and reoxygenation induced oxidative stress lead to immunosuppression and apoptosis in golden pompano (Trachinotus blochii) - Yue Gu; Jun Long Sun; Fu Cheng Yao; Tian Jiang; Chun Xiu Jin; Li Ping Shi; Shu Kui Sun; Fei Biao Song; Jian Luo (Frontiers in Marine Science, 2023)
The fluctuations of dissolved oxygen (DO) often lead to hypoxia in aquaculture, which has a huge adverse impact on fish. This study mainly investigated the effects of long-term hypoxia on oxidative stress, immune response, and cell apoptosis in the liver of golden pompano ( Trachinotus blochii ), which is not tolerant to hypoxia. So we conducted a 14 day low oxygen stress experiment on the golden pompano with a DO of 3.0 ± 0.2 mg/L, then restore the DO to normal levels and continue the 14 day reoxygenation experiment. Results showed that hypoxia and reoxygenation led to significant changes in liver structure. During hypoxia and reoxygenation, the expression of oxidative stress related genes ( SOD1 , SOD2 , GSH-Px , and CAT ) and levels of antioxidant enzymes (CAT and MDA) in the liver were increased. Liver lysozyme activity and the relative expression of the pro-inflammatory factors interleukin ( IL)-1β were significantly increased, but the expression of IL-34 was down-regulated during hypoxia. The expression of IL-12β was significantly increased during reoxygenation. The expression of anti-inflammatory factor IL -11 was decreased duringreoxygenation. The expression of toll like receptors ( TLRs ) -7, -8, and -9 increases after hypoxia and decreases after reoxygenation, indicating that both hypoxia and reoxygenation affect the immune response. In addition, during hypoxia and reoxygenation, TUNEL-positive signals increased, the bcl2/bax ratio decreased, the expression levels of caspases-3 and -8 were significantly up-regulated during hypoxia, and expression levels of caspases-9 was up-regulated during reoxygenation. In summary, hypoxia and reoxygenation can cause oxidative stress, induce inflammatory reactions, inhibit immune processes, activate apoptosis, and lead to liver damage of the golden pompano, which may be irreversible.

In situ prepared Chlorella vulgaris–supported nanoscale zero-valent iron to remove arsenic (III) - Tingting Yue; Yuankun Yang; Shu Chen; Jun Yao; Huili Liang; Liang Jia; Kaibin Fu; Zhe Wang (Environmental Science and Pollution Research, 2023)

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

Characterization of microbial contamination of retail washed and unwashed shell eggs in Taiwan - Shu-Chen Hsu; Hsiu-Ling Chen; Chin-Fu Chou; Wen-Chun Liu; Chen-Ting Wu (Food Control, 2023)

Tartary buckwheat flavonoids alleviates high-fat diet induced kidney fibrosis in mice by inhibiting MAPK and TGF-β1/Smad signaling pathway - Shu Liu; Shoupeng Fu; Yuhang Jin; Ruiqi Geng; Yuhang Li; Yufei Zhang; Juxiong Liu; Wenjin Guo (Chemico-Biological Interactions, 2023)

Investigating the causes of O3 pollution in the western rim of sichuan basin, southwestern China - Xi Shu; Zhonglin Xia; Qi Ying; Yuhan Fu; Xue Qiao; Ya Tang (Atmospheric Pollution Research, 2023)

Attenuation of mountain-valley circulations on PM2.5 pollution over the western Sichuan basin, southwest China - Yuqing Zhang; Tianliang Zhao; Zhuozhi Shu; Dingyuan Liang; Weikang Fu; Yan Zhu (Atmospheric Pollution Research, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

Isolation and structure determination of superbcyclin A, a cyclic nonapeptide from Dianthus superbus - Qing Zhang; Jing-Hui Yang; Yu-Lan Du; Xu-Yang Fu; Wu-Yang Liu; Yi-Qin Zeng; Shu-Hui Liu; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry Letters, 2023)

Changes of atmospheric metal(loid) deposition from 2017 to 2021 at Mount Emei under China's air pollution control strategy - Yuhan Fu; Ya Tang; Xi Shu; Philip K. Hopke; Lei He; Qi Ying; Zhonglin Xia; Mengjie Lei; Xue Qiao (Atmospheric Environment, 2023)

The Intrinsic Relation between the Hydrogel Structure and In Vivo Performance of Hyaluronic Acid Dermal Fillers: A Comparative Study of Four Typical Dermal Fillers - Weiwei Zhou; Shuai Hou; Shu Deng; Yang Peng; Wei Fu; Yang Zhou; Jie Yang; Cheng Peng (Tissue Engineering and Regenerative Medicine, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

NECL2 regulates blood–testis barrier dynamics in mouse testes - Jun Fu; Xiao Liu; Bin Yin; Pengcheng Shu; Xiaozhong Peng (Cell and Tissue Research, 2023)

Causes of the discordance in the south-north distribution of the 2017 Jiuzhaigou earthquake sequences - Zhi-Tong Jin; Jia-Lu Liu; Yong-Ge Wan; Shu-Zhong Sheng; Fu-Chang Wang; Xiao-Tao Zhang; Gan Feng (Applied Geophysics, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Revealing the potential of organo-mineral complexes in agricultural application using bibliometrics - Xuehao Zheng; Belay Tafa Oba; Han Wang; Bin Zhang; Chengqiang Shu; Yan Song; Jianfeng Fu; Shejiang Liu; Yuxin Zhang; Nan Dai; Dan Song; Hui Ding (Journal of Cleaner Production, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Modeling the Operating Performance of a Drinking Water Biological Aerated Filter and the Formation of Organic Nitrogen - Jia Kang; Chu-qiong Song; Ning Zhou; Yao-wen Zhang; Shu-li Liu; Gang-fu Song; Wa-ni Zhou (Environmental Science and Pollution Research, 2023)

Codependent failure mechanisms between cathode and anode in solid state lithium metal batteries: mediated by uneven ion flux - Yue Zheng; Shu Zhang; Jun Ma; Fu Sun; Markus Osenberg; André Hilger; Henning Markötter; Fabian Wilde; Ingo Manke; Zhongbo Hu; Guanglei Cui (Science Bulletin, 2023)

The spatial configuration of buildings: A vital consideration impossible to ignore in regulating urban land surface temperature? Evidence from 35 Chinese cities - Wei Chen; Jianjun Zhang; Shidong Liu; Sen Liang; Yaping Zhang; Shu Fu (Science of The Total Environment, 2023)

One-pot synthesis of ternary-emission molecularly imprinted fluorescence sensor based on metal–organic framework for visual detection of chloramphenicol - Xiaodan Wu; Sisi Tang; Pengfei Zhao; Kangling Tang; Yu Chen; Jinli Fu; Shu Zhou; ZhaoXia Yang; Zhaohui Zhang (Food Chemistry, 2023)

Bilateral asymmetry of otoliths from Collichthys lucidus of different sizes in Haizhou Bay and Xiangshan Bay - Shuo Zhang; Xiao Zhang; Shike Gao; Ruilin Shu; Guanghui Fu; Jikun Lu (Journal of Fish Biology, 2023)
In recent years, the frequent occurrence of most human activities has seriously affected the structure and functioning of coastal ecosystems. The asymmetric relationship between the left and right otoliths of fish is often used to test the difference in fluctuating asymmetry (FA) reflected by the square of the coefficient of asymmetric variation ( CV 2 a ), which can be regarded as an important step in the study of marine environmental pressure and implementation of offshore ecological restoration. In this study, the authors tested the bilateral FA of Collichthys lucidus in the coastal waters of Haizhou Bay, Jiangsu, and Xiangshan Bay, Zhejiang, China, using four sagittal otolith characters (length, width, perimeter and area) as biological characters. The results showed that the value of CV 2 a in otolith width (more sensitive to environmental pressure) of C. lucidus in Xiangshan Bay was higher than that in Haizhou Bay, indicating that the environmental pressure on Xiangshan Bay was relatively high. The authors did not find any significant differences in the FA of otoliths between different body sizes of C. lucidus , which may be related to the short‐distance migration in different regions and the dietary shifts in the life history of this species. The results have conservation and management implications for this population.

Poly(caffeic acid) as interlayer to enhance nanofiltration performance of polyamide composite membrane - Xiao-lei Wang; Ya-xian Xue; Shu-qian Dong; Qi Wang; Jiang-tao Yu; Hui-cai Wang; Huan Zhang; Wan Wang; Jun-fu Wei (Desalination, 2023)

Evaluation of LiNiO2 with minimal cation mixing as a cathode for Li-ion batteries - Rio Akbar Yuwono; Fu-Ming Wang; Nae-Lih Wu; Yan-Cheng Chen; Hsi Chen; Jin-Ming Chen; Shu-Chih Haw; Jyh-Fu Lee; Rui-Kun Xie; Hwo-Shuenn Sheu; Po-Ya Chang; Chusnul Khotimah; et al. (Chemical Engineering Journal, 2023)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Evolution stage, spatial and temporal variabilities of granite landforms in the Mount Wugongshan in Jiangxi Province of South China - Le Chai; Cun-di Zhong; Fu-sheng Guo; Xin-shu Huang; Dao-ying Wang; Chong-jian Shao; Liu-qin Chen (Journal of Mountain Science, 2022)

Sustainable Approaches to Realize Carbon Neutrality in China: A Case Study of Zhejiang Province - Yuexuan Shu; Jiwei Chen; Yifan Huang; Weiqi Fu (Journal of Marine Science and Engineering, 2022)
With the continuous development of industry, the massive emission of carbon dioxide (CO2) has become a global challenge that cannot be ignored due to its nature as the primary driver of global climate change and environmental crisis. Carbon neutrality is proposed as a global initiative to mitigate climate change. As a developing industrial country, China provides about one-third of global carbon emissions and has set a carbon-neutral goal by 2060. To achieve this goal, continuous efforts across the country are required. In this review, Zhejiang Province, one of the most developed regions in China, is set as a model for analysis. We first summarize the current situation of carbon emission in Zhejiang Province. Then, corresponding sustainable approaches such as ecological and industrial solutions for the reduction of future carbon emissions are introduced for Zhejiang Province. We also provide a direction for the realization of carbon neutrality, focusing on the most promising solutions for Zhejiang Province.

Blockchain-enhanced trading systems for construction industry to control carbon emissions - Zhan Shu; Wenhao Liu; Bailu Fu; Zheng Li; Minjuan He (Clean Technologies and Environmental Policy, 2022)

Climate Warming Mitigation from Nationally Determined Contributions - Bo Fu; Jingyi Li; Thomas Gasser; Philippe Ciais; Shilong Piao; Shu Tao; Guofeng Shen; Yuqin Lai; Luchao Han; Bengang Li (Advances in Atmospheric Sciences, 2022)

Fengyun-4 Geostationary Satellite-Based Solar Energy Nowcasting System and Its Application in North China - Chunlin Huang; Hongrong Shi; Ling Gao; Mengqi Liu; Qixiang Chen; Disong Fu; Shu Wang; Yuan Yuan; Xiang’ao Xia (Advances in Atmospheric Sciences, 2022)

Application of an improved hollow fiber liquid phase microextraction technique coupled to LC-MS/MS to studying migration of fluorescent whitening agents from plastic food contact materials - Wen-Li Zhou; Li Ding; Yun-Hui Cheng; Zhou Xu; Mao-Long Chen; Xian-Shu Fu (Food Additives & Contaminants: Part A, 2022)

Vertically grown CeO2 and TiO2 nanoparticles over the MIL53Fe MOF as proper band alignments for efficient H2 generation and 2,4-DCP degradation - Muhammad Humayun; Lang Shu; Wenbo Pi; Hui Xia; Abbas Khan; Zhiping Zheng; Qiuyun Fu; Yahui Tian; Wei Luo (Environmental Science and Pollution Research, 2022)

Development of modified integrated water quality index to assess the surface water quality: a case study of Tuo River, China - Dong Fu; Shu Chen; Yongcan Chen; Zhenyan Yi (Environmental Monitoring and Assessment, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

Correction to: Chitosan‑based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu‑Wei Huang; Fang‑Ching Yeh; You‑Ren Ji; Ying‑Fu Su; Ying‑shih Su; Ming‑Hsien Chiang; Shian‑Chiuan Tzeng; Chien‑Yao Fu; Aristine Cheng; Yung‑Chih Wang; Yi‑Tzu Lee (Drug Delivery and Translational Research, 2022)

The beneficial roles of poisonous skin secretions in survival strategies of the odorous frog Odorrana andersonii - Naixin Liu; Buliang Meng; Wenxin Bian; Meifeng Yang; Longjun Shu; Yixiang Liu; Zhe Fu; Yinglei Wang; Ying Wang; Xinwang Yang (The Science of Nature, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Spectral characterization of the effect of gas–water ratio on dissolved organic nitrogen variation along a drinking water biological aerated filter - Jia Kang; Gang-fu Song; Shu-li Liu; Chu-qiong Song; Xu Gao (Environmental Science and Pollution Research, 2021)

Methacrylic functionalized hybrid carbon nanomaterial for the selective adsorption and detection of progesterone in wastewater - Xia Cui; Hua Shu; Lu Wang; Guoning Chen; Jili Han; Qianqian Hu; Kamran Bashir; Zhimin Luo; Chun Chang; Jia Zhang; Qiang Fu (Environmental Science and Pollution Research, 2021)

Dynamics of antibiotic resistance and its association with bacterial community in a drinking water treatment plant and the residential area - Fu-Yi Huang; Qing-Lin Chen; Xian Zhang; Roy Neilson; Jian-Qiang Su; Shu-Yi-Dan Zhou (Environmental Science and Pollution Research, 2021)

Ecological carrying capacity of alpine grassland in the Qinghai–Tibet Plateau based on the structural dynamics method - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jiang Ding (Environment, Development and Sustainability, 2021)

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu-Wei Huang; Fang-Ching Yeh; You-Ren Ji; Ying-Fu Su; Ying-shih Su; Ming-Hsien Chiang; Shian-Chiuan Tzeng; Chien-Yao Fu; Aristine Cheng; Yung-Chih Wang; Yi-Tzu Lee (Drug Delivery and Translational Research, 2021)

Numerical Investigation to the Effect of Suction-Induced Seepage on the Settlement in the Underwater Vacuum Preloading with Prefabricated Vertical Drains - Shu Lin; Dengfeng Fu; Zefeng Zhou; Yue Yan; Shuwang Yan (Journal of Marine Science and Engineering, 2021)
Vacuum preloading combined with prefabricated vertical drains (PVDs) has the potential to improve the soft sediments under water, however, its development is partly limited by the unclear understanding of the mechanism. This paper aims to extend the comprehension of the influential mechanism of overlapping water in the scenario of underwater vacuum preloading with PVDs. The systematic investigations were conducted by small strain finite element drained analyses, with the separated analysis schemes considering suction-induced consolidation, seepage and their combination. The development of settlement in the improved soil region and the evolution of seepage flow from the overlapping water through the non-improved soil region into improved zone are examined in terms of the build-up of excess pore pressure. Based on the results of numerical analyses, a theoretical approach was set out. It was capable to estimate the time-dependent non-uniform settlement along the improved soil surface in response to the combined effects of suction-induced consolidation and seepage. The difference of underwater and onshore vacuum preloading with PVDs is discussed with some practical implication and suggestion provided.

The geochemical behavior of trace metals and nutrients in submerged sediments of the Three Gorges Reservoir and a critical review on risk assessment methods - Bin Wang; Shu Chen; Yuwei Chen; Nelson Belzile; Rui Zheng; Yuankun Yang; Kaibin Fu; Yongcan Chen; Binliang Lin; Zhaowei Liu; Jian Sun (Environmental Science and Pollution Research, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Lactobacillus rhamnosus JYLR-005 Prevents Thiram-Induced Tibial Dyschondroplasia by Enhancing Bone-Related Growth Performance in Chickens - Fang Liu; Anan Kong; Pengfei Fu; Qin-qin Cao; Kun-sheng Tao; Di-yi Liu; Xue-bing Wang; Zong-xi Tong; Mujeeb Ur Rehman; Shu-cheng Huang (Probiotics and Antimicrobial Proteins, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Calculating the sediment flux of the small coastal watersheds: a modification of global equations - Gaocong Li; Qiong Xia; Dongyang Fu; Chunhua Zeng; Zhiqiang Li; Shu Gao (Acta Oceanologica Sinica, 2021)

An ignored key link in greenhouse effect: Soil and soil CO2 slow heat loss - Weixin Zhang; Chengde Yu; Zhifeng Shen; Shu Liu; Suli Li; Yuanhu Shao; Shenglei Fu (Soil Ecology Letters, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Environmental impact of Hsuehshan Tunnel on water quality at Feitsui Reservoir and its tributaries - Tai-Tien Wang; Fu-Shu Jeng; Tzu-Tung Lee (Environmental Monitoring and Assessment, 2020)

Identifying genes for resistant starch, slowly digestible starch, and rapidly digestible starch in rice using genome-wide association studies - Ning Zhang; Maike Wang; Ji Fu; Yi Shen; Yi Ding; Dianxing Wu; Xiaoli Shu; Wenjian Song (Genes & Genomics, 2020)

Nanostructure of DiR-Loaded Solid Lipid Nanoparticles with Potential Bioimaging Functions - Lei Shu; Fangqin Fu; Zhengwei Huang; Ying Huang; Ping Hu; Xin Pan (AAPS PharmSciTech, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Identification of a novel mutant spp1 that specifies the identity of inflorescence meristem in rice - Peizhou Xu; Asif Ali; Yun Li; Hongyu Zhang; Xiaoqiong Chen; Shaohong Fu; Yang Jin; Zhongwei Zhang; Shu Yuan; Xianjun Wu (Plant Biosystems, 2020)

Impact of urbanization on hydrological processes under different precipitation scenarios - Wenbin Zang; Shu Liu; Shifeng Huang; Jiren Li; Yicheng Fu; Yayong Sun; Jingwei Zheng (Natural Hazards, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Correction to: A newly developed APCC SCoPS and its prediction of East Asia seasonal climate variability - Suryun Ham; A-Young Lim; Suchul Kang; Hyein Jeong; Yeomin Jeong; Bin Wang; Baoqiang Xiang; Shu Wu; Joshua Xiouhua Fu (Climate Dynamics, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Improved Jayaweera-Mikkelsen model to quantify ammonia volatilization from rice paddy fields in China - Xiaoying Zhan; Chuan Chen; Qihui Wang; Feng Zhou; Kentaro Hayashi; Xiaotang Ju; Shu Kee Lam; Yonghua Wang; Yali Wu; Jin Fu; Luping Zhang; Shuoshuo Gao; et al. (Environmental Science and Pollution Research, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Cerebrospinal fluid otorrhea secondary to congenital inner ear dysplasia: diagnosis and management of 18 cases - Bing Wang; Wen-jia Dai; Xiao-ting Cheng; Wen-yi Liuyang; Ya-sheng Yuan; Chun-fu Dai; Yi-lai Shu; Bing Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Role of permafrost in resilience of social-ecological system and its spatio-temporal dynamics in the source regions of Yangtze and Yellow Rivers - Yi-ping Fang; Fu-biao Zhu; Shu-hua Yi; Xiao-ping Qiu; Yong-jian Ding (Journal of Mountain Science, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Down-regulation of microRNA-216a confers protection against yttrium aluminium garnet laser-induced retinal injury via the GDNF-mediated GDNF/GFRα1/RET signalling pathway - Xi-Bin Hu; Shu-Hua Fu; Qi Luo; Jian-Zhong He; Yan-Fei Qiu; Wei Lai; Min Zhong (Journal of Biosciences, 2018)

High-resolution melting-based TILLING of γ ray-induced mutations in rice - Shan Li; Song-mei Liu; Hao-wei Fu; Jian-zhong Huang; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2018)

Haploid plant regeneration from hardy kiwifruit (Actinidia arguta Planch.) anther culture - Guang-Fu Wang; Hong-Yan Qin; Dan Sun; Shu-Tian Fan; Yi-Ming Yang; Zhen-Xing Wang; Pei-Llei Xu; Ying Zhao; Ying-Xue Liu; Jun Ai (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Variable hydrological effects of herbs and shrubs in the arid northeastern Qinghai-Tibet Plateau, China - Ya-bin Liu; Ying Zhang; Jiang-tao Fu; Dong-mei Yu; Xia-song Hu; Xi-lai Li; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Prodigiosin stimulates endoplasmic reticulum stress and induces autophagic cell death in glioblastoma cells - Shu-Yu Cheng; Nan-Fu Chen; Hsiao-Mei Kuo; San-Nan Yang; Chun-Sung Sung; Ping-Jyun Sung; Zhi-Hong Wen; Wu-Fu Chen (Apoptosis, 2018)

Eriodictyol protects against Staphylococcus aureus-induced lung cell injury by inhibiting alpha-hemolysin expression - He Xuewen; Ouyang Ping; Yuan Zhongwei; Yin Zhongqiong; Fu Hualin; Lin Juchun; He Changliang; Shu Gang; Yuan Zhixiang; Song Xu; Zou Yuanfeng; Li Lixia; et al. (World Journal of Microbiology and Biotechnology, 2018)

Microarray expression profiling and co-expression network analysis of circulating LncRNAs and mRNAs associated with neurotoxicity induced by BPA - Wei Pang; Fu-Zhi Lian; Xue Leng; Shu-min Wang; Yi-bo Li; Zi-yu Wang; Kai-ren Li; Zhi-xian Gao; Yu-gang Jiang (Environmental Science and Pollution Research, 2018)

Novel method for iron recovery from hazardous iron ore tailing with induced carbothermic reduction-magnetic flocculation separation - Shao-Jun Bai; Chun-Long Li; Xiang-Yu Fu; Chao Lv; Shu-Ming Wen (Clean Technologies and Environmental Policy, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Associations between total mercury and methyl mercury exposure and cardiovascular risk factors in US adolescents - Yuxi Zhang; Cheng Xu; Zhi Fu; Yaqin Shu; Jie Zhang; Changgui Lu; Xuming Mo (Environmental Science and Pollution Research, 2018)

A new wortmannine derivative from a Tripterygium wilfordii endophytic fungus Talaromyces wortmannii LGT-4 - Jing-Yun Sun; Zhong-Duo Yang; Guang-Chao Fu; Yong-Gang Wang; Hong-Yan Xue; Zong-Mei Shu (Natural Product Research, 2017)

Chronological constraints on the tectonic evolution of the Chinese Tianshan Orogen through detrital zircons from modern and palaeo-river sands - Rong Ren; Shu-Wei Guan; Bao-Fu Han; Li Su (International Geology Review, 2017)

An analysis of patents for anesthetic laryngoscopes - Cheng-dong Ji; Xin Pan; Yuan-chang Xiong; Xuan Guo; Shu-wen Qian; Chang Xu; Qiang-qiang Fu; Zhi-ping Yang; Yu Ma; Yue-zhu Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Simple additive simulation overestimates real influence: altered nitrogen and rainfall modulate the effect of warming on soil carbon fluxes - Xiangyin Ni; Wanqin Yang; Zemin Qi; Shu Liao; Zhenfeng Xu; Bo Tan; Bin Wang; Qinggui Wu; Changkun Fu; Chengming You; Fuzhong Wu (Global Change Biology, 2017)
Experiments and models have led to a consensus that there is positive feedback between carbon (C) fluxes and climate warming. However, the effect of warming may be altered by regional and global changes in nitrogen (N) and rainfall levels, but the current understanding is limited. Through synthesizing global data on soil C pool, input and loss from experiments simulating N deposition, drought and increased precipitation, we quantified the responses of soil C fluxes and equilibrium to the three single factors and their interactions with warming. We found that warming slightly increased the soil C input and loss by 5% and 9%, respectively, but had no significant effect on the soil C pool. Nitrogen deposition alone increased the soil C input (+20%), but the interaction of warming and N deposition greatly increased the soil C input by 49%. Drought alone decreased the soil C input by 17%, while the interaction of warming and drought decreased the soil C input to a greater extent (−22%). Increased precipitation stimulated the soil C input by 15%, but the interaction of warming and increased precipitation had no significant effect on the soil C input. However, the soil C loss was not significantly affected by any of the interactions, although it was constrained by drought (−18%). These results implied that the positive C fluxes–climate warming feedback was modulated by the changing N and rainfall regimes. Further, we found that the additive effects of [warming × N deposition] and [warming × drought] on the soil C input and of [warming × increased precipitation] on the soil C loss were greater than their interactions, suggesting that simple additive simulation using single‐factor manipulations may overestimate the effects on soil C fluxes in the real world. Therefore, we propose that more multifactorial experiments should be considered in studying Earth systems.

Physiological and transcriptional analysis reveals pathways involved in iron deficiency chlorosis in fragrant citrus - Long-Fei Jin; Yong-Zhong Liu; Wei Du; Li-Na Fu; Syed Bilal Hussain; Shu-Ang Peng (Tree Genetics & Genomes, 2017)

Serum Protein-Based Profiles as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease - Shu Yu; Yue-Ping Liu; Hai-Liang Liu; Jie Li; Yang Xiang; Yu-Hui Liu; Shu-Sheng Jiao; Lu Liu; Yajiang Wang; Weiling Fu (Molecular Neurobiology, 2017)

High‐frequency daily temperature variability in China and its relationship to large‐scale circulation - Fu‐Ting Wu; Congbin Fu; Yun Qian; Yang Gao; Shu‐Yu Wang (International Journal of Climatology, 2017)
Two measures of intra‐seasonal variability, indicated respectively by standard deviations ( SD ) and day‐to‐day ( DTD ) fluctuations denoted by absolute differences between adjacent 2‐day periods, as well as their relationships with large‐scale circulation patterns were investigated in China during 1962–2008 on the basis of homogenized daily temperature records from 549 local stations and reanalysis data. Our results show that both the SD and DTD of daily minimum temperatures ( T min ) in summer as well as the minimum and maximum temperatures in winter have been decreasing, while the daily maximum temperature ( T max ) variability in summer is fluctuating more, especially over southern China. In summer, an attribution analysis indicates that the intensity of the Western Pacific Subtropical High ( WPSH ) and high‐level East Asian Subtropical Jet stream ( EASJ ) are positively correlated with both SD and DTD , but the correlation coefficients are generally greater with the SD than with the DTD of the daily maximum temperature, T max . In contrast, the location of the EASJ shows the opposite correlation pattern, with intensity regarding the correlation with both SD and DTD . In winter, the Arctic Oscillation ( AO ) is negatively correlated with both the SD and DTD of the daily minimum temperature, but its intra‐seasonal variability exhibits good agreement with the SD of the T min . The Siberian High acts differently with respect to the SD and DTD of the T min , demonstrating a regionally consistent positive correlation with the SD . Overall, the large‐scale circulation can well explain the intra‐seasonal SD, but DTD fluctuations may be more local and impacted by local conditions, such as changes in the temperature itself, the land surface, and so on.

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

Frequency and type of inheritable mutations induced by γ rays in rice as revealed by whole genome sequencing - Shan Li; Yun-chao Zheng; Hai-rui Cui; Hao-wei Fu; Qing-yao Shu; Jian-zhong Huang (Journal of Zhejiang University-SCIENCE B, 2016)

Smoking and Serum Lipid Profiles in Schizophrenia - Hui-Mei An; Yun-Long Tan; Shu-ping Tan; Jing Shi; Zhi-Ren Wang; Fu-De Yang; Xu-Feng Huang; Jair C. Soars; Thomas R. Kosten; Xiang-Yang Zhang (Neuroscience Bulletin, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Diversity of phototrophic phytoplankton in Northern South China Sea indicated by rbcL analysis - Nan Li; Shu-Xian Yu; Yin-Chu Wang; Jia-Lin Li; Fu-Chao Li; Song Qin (Journal of Applied Phycology, 2016)

Isolation and identification of a new reovirus associated with mortalities in farmed oriental river prawn, M acrobrachium nipponense (de Haan, 1849), in C hina - S Zhang; X Shu; L Zhou; B Fu (Journal of Fish Diseases, 2016)

Effects of cigarette smoking and alcohol use on neurocognition and BDNF levels in a Chinese population - Xiang Yang Zhang; Yun-Long Tan; Da-Chun Chen; Shu-Ping Tan; Fu-De Yang; Giovana B. Zunta-Soares; Jair C Soares (Psychopharmacology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Nitrogen removal and water microbiota in grass carp culture following supplementation with Bacillus licheniformis BSK-4 - Quan Liang; Xiaoping Zhang; Khui Hung Lee; Yibing Wang; Kan Yu; Wenying Shen; Luoqin Fu; Miaoan Shu; Weifen Li (World Journal of Microbiology and Biotechnology, 2015)

Protective Roles of Selenium on Nitric Oxide and the Gene Expression of Inflammatory Cytokines Induced by Cadmium in Chicken Splenic Lymphocytes - Shuang Liu; Fengping Xu; Jing Fu; Shu Li (Biological Trace Element Research, 2015)

Isolation and characterization of a crude oil degrading bacteria from formation water: comparative genomic analysis of environmental Ochrobactrum intermedium isolate versus clinical strains - Lu-jun Chai; Xia-wei Jiang; Fan Zhang; Bei-wen Zheng; Fu-chang Shu; Zheng-liang Wang; Qing-feng Cui; Han-ping Dong; Zhong-zhi Zhang; Du-jie Hou; Yue-hui She (Journal of Zhejiang University-SCIENCE B, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Substrate specificity and biochemical characterization of an adenylation domain from an obligate marine actinomycete - Xiao Shu; Yanling Ma; Chong Lu; Ming Lei; Yanli Liu; Ke Liu; Guomei Xiong; Sisi Xia; Zhijuan Zhao; Wenkai Luo; Qiao Fu; Chao Qi (Biotechnology Letters, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Association of ACP1 gene polymorphisms and coronary artery disease in northeast Chinese population - TIANBAO LI; XUESONG XU; JIANZHUO LI; SHU XING; LIN ZHANG; WANNAN LI; JUNFENG MA; XUEQI FU (Journal of Genetics, 2015)

Expression of cytochrome P450 CYP81A6 in rice: tissue specificity, protein subcellular localization, and response to herbicide application - Hai-ping Lu; Martin Edwards; Qi-zhao Wang; Hai-jun Zhao; Hao-wei Fu; Jian-zhong Huang; Angharad Gatehouse; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2015)

Decreased serum TNF-alpha levels in chronic schizophrenia patients on long-term antipsychotics: correlation with psychopathology and cognition - Meng Han Lv; Yun Long Tan; Shao Xiao Yan; Li Tian; Da Chun Chen; Shu Ping Tan; Zhi Ren Wang; Fu De Yang; Jin H. Yoon; Giovana B. Zunta-Soares; Jair C. Soares; Xiang Yang Zhang (Psychopharmacology, 2015)

The genus Codonopsis (Campanulaceae): a review of phytochemistry, bioactivity and quality control - Jing-Yu He; Na Ma; Shu Zhu; Katsuko Komatsu; Zhi-Yuan Li; Wei-Ming Fu (Journal of Natural Medicines, 2015)
Codonopsis , in the family Campanulaceae, is a genus containing 42 species of dicotyledonous herbaceous perennial plants, predominantly found in Central, East and South Asia. Several Codonopsis species are widely used in traditional medicine and are considered to have multiple medicinal properties. Among the Codonopsis species, Codonopsis pilosula (Franch.) Nannf. and C. lanceolata (Sieb. et Zucc.) Benth. & Hook. f. ex Trautv. are more popular than others according to the findings, especially phytochemical and bioactive studies. Phytochemical research shows that Codonopsis species contain mainly polyacetylenes, phenylpropanoids, alkaloids, triterpenoids and polysaccharides, which contribute to multiple bioactivities. However, the mechanisms of their bioactivities need to be further elucidated. The less popular Codonopsis species remain to be studied and exploited. In addition, although a series of methods for the quality evaluation of Codonopsis species have been developed, a feasible and reliable approach to the efficacious and safe use of various Codonopsis species is still needed, with considering botanical origin, chemical constituents and bioactive effects. This review aims to provide up-to-date and comprehensive information on the phytochemistry, bioactivity and quality control of medicinal plants in the genus Codonopsis and to highlight current gaps in knowledge, which is useful for the wider development of the Codonopsis genus.

Differences in boron distribution and forms in four citrus scion–rootstock combinations with contrasting boron efficiency under boron-deficient conditions - Nannan Wang; Tingshuai Yan; Lina Fu; Gaofeng Zhou; Yongzhong Liu; Shu’ang Peng (Trees, 2014)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Relationship between gene expression of UDP-glucose pyrophosphorylase and agar yield in Gracilariopsis lemaneiformis (Rhodophyta) - Lianpeng Chang; Zhenghong Sui; Feng Fu; Wei Zhou; Jinguo Wang; Kyoung Ho Kang; Shu Zhang; Jinhua Ma (Journal of Applied Phycology, 2014)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Contamination and distribution of parent, nitrated, and oxygenated polycyclic aromatic hydrocarbons in smoked meat - Yuanchen Chen; Guofeng Shen; Shu Su; Huizhong Shen; Ye Huang; Tongchao Li; Wei Li; Yanyan Zhang; Yan Lu; Han Chen; Chunli Yang; Nan Lin; et al. (Environmental Science and Pollution Research, 2014)

Effect of photosynthetic bacteria on water quality and microbiota in grass carp culture - Xiaoping Zhang; Miaoan Shu; Yibing Wang; Luoqin Fu; Weifen Li; Bin Deng; Quan Liang; Wenying Shen (World Journal of Microbiology and Biotechnology, 2014)

The extracts of Holotrichia diomphalia larvae inhibit proliferation and induce apoptosis of cancer cells in vitro and in vivo - Lianlian Song; Shu Sun; Longnan Jin; Lijuan Xue; Yaowen Fu (Molecular & Cellular Toxicology, 2014)

Modified high-intensity interval training increases peak cardiac power output in patients with heart failure - Shu-Chun Huang; Mei-Kuen Wong; Pyng-Jing Lin; Feng-Chun Tsai; Tieh-cheng Fu; Ming-Shien Wen; Chi-Tai Kuo; Jong-Shyan Wang (European Journal of Applied Physiology, 2014)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

The Application of Water Quality Monitoring Data in a Reservoir Watershed Using AMOS Confirmatory Factor Analyses - Edward Ming-Yang Wu; Chia Cheng Tsai; Juey Fu Cheng; Shu Lung Kuo; Wei Ting Lu (Environmental Modeling & Assessment, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Enhanced methane hydrate storage using sodium dodecyl sulfate and coal - Shu-Qing Hao; Sungho Kim; Yong Qin; Xue-Hai Fu (Environmental Chemistry Letters, 2014)

Isolation and characterization of microsatellite loci in Euphorbia lamarckii Sweet (Euphorbiaceae) from the Canary Islands - Yan-Shu Li; Ye Sun; Fa-Guo Wang; Fu-Wu Xing (Conservation Genetics Resources, 2014)

Occurrence and removal of six pharmaceuticals and personal care products in a wastewater treatment plant employing anaerobic/anoxic/aerobic and UV processes in Shanghai, China - Dan Wang; Qian Sui; Shu-Guang Lu; Wen-Tao Zhao; Zhao-Fu Qiu; Zhou-Wei Miao; Gang Yu (Environmental Science and Pollution Research, 2014)

UV-irradiation mutation of tetraspores of Gracilariopsis lemaneiformis and screening of thermotolerant strains - Feng Fu; Zheng-Hong Sui; Wei Zhou; Jin-Guo Wang; Lian-Peng Chang; Shu-Fang Ci (Journal of Applied Phycology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Verapamil Reverses Myocardial No-Reflow After Primary Percutaneous Coronary Intervention in Patients with Acute Myocardial Infarction - Qiang Fu; Wen Lu; Yi-jie Huang; Qiang Wu; Lin-guang Wang; Hai-bo Wang; Shu-zhong Jiang; Yan-jiong Wang (Cell Biochemistry and Biophysics, 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

A Pyrene-based Highly Selective Turn-on Fluorescent Chemosensor for Iron(III) Ions and its Application in Living Cell Imaging - Peter Kun Chung; Shi-Rong Liu; Hsuan-Fu Wang; Shu-Pao Wu (Journal of Fluorescence, 2013)

Polymorphisms in MHC class Ia genes and resistance to IHNV in rainbow trout (Oncorhynchus mykiss) - Zhe Liu; Dan Dan Hu; Shu Juan Shao; Juan Yang; Jian Fu Wang; Jin Qiang Huang (Genes & Genomics, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Distributions, sources, and ecological risks of hexachlorocyclohexanes in the sediments from Haihe Plain, Northern China - Fu-Liu Xu; Xiang-Zhen Kong; Wei He; Ning Qin; Ying Zhu; Shu Tao (Environmental Science and Pollution Research, 2013)

Trace Element, Antioxidant Activity, and Lipid Peroxidation Levels in Brain Cortex of Gerbils After Cerebral Ischemic Injury - Kwang-Ming Fang; Fu-Chou Cheng; Yeou-Lih Huang; Shu-Ying Chung; Zhong-Yang Jian; Ming-Cheng Lin (Biological Trace Element Research, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

A new species of Gyraulus (Gastropoda: Planorbidae) from Ancient Lake Lugu, Yunnan-Guizhou Plateau, Southwest China - Fengyue Shu; Frank Köhler; Cuichang Fu; Hongzhu Wang (Molluscan Research, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

Distributions, sources, and ecological risks of DDT-related contaminants in water, suspended particulate matter, and sediments from Haihe Plain, Northern China - Yan Wang; Wei He; Ning Qin; Qi-Shuang He; Xiang-Zhen Kong; Shu Tao; Fu-Liu Xu (Environmental Monitoring and Assessment, 2013)

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation - Ming-Wei Wang; Fang Wang; Yu-Jia Zheng; Ying-Jian Zhang; Yong-Ping Zhang; Qing Zhao; Clifton Kwang-Fu Shen; Yue Wang; Shu-Han Sun (Apoptosis, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Molecular Cloning and Characterization of Two 9-Lipoxygenase Genes from Taxus chinensis - Shu-tao Li; Meng Zhang; Chun-hua Fu; Sha Xie; Yu Zhang; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Enhancing Taxol Biosynthesis by Overexpressing a 9-Cis-Epoxycarotenoid Dioxygenase Gene in Transgenic Cell Lines of Taxus chinensis - Shu-tao Li; Chun-hua Fu; Meng Zhang; Yu Zhang; Sha Xie; Long-jiang Yu (Plant Molecular Biology Reporter, 2012)

Tomographic inversion for microseismic source parameters in mining - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

Anomalous temperature–growth response of Abies faxoniana to sustained freezing stress along elevational gradients in China’s Western Sichuan Province - Zong Shan Li; Guo Hua Liu; Bo Jie Fu; Chan Juan Hu; Shu Zheng Luo; Xing Liang Liu; Fei He (Trees, 2012)

Structural insights into a human anti-IFN antibody exerting therapeutic potential for systemic lupus erythematosus - Songying Ouyang; Bin Gong; Jin-Zhi Li; Li-Xia Zhao; Wei Wu; Fu-Shun Zhang; Lina Sun; Shu-Jun Wang; Meng Pan; Chuan Li; Wenguang Liang; Neil Shaw; et al. (Journal of Molecular Medicine, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Exploration of biguanido–oxovanadium complexes as potent and selective inhibitors of protein tyrosine phosphatases - Liping Lu; Xiaoli Gao; Miaoli Zhu; Sulian Wang; Qiong Wu; Shu Xing; Xueqi Fu; Zhiwei Liu; Maolin Guo (BioMetals, 2012)

Automatically positioning microseismic sources in mining by the stereo tomographic method using full wavefields - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Jian-Yong Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Induced pluripotent stem cell-related genes influence biological behavior and 5-fluorouracil sensitivity of colorectal cancer cells - Zhong Shi; Rui Bai; Zhi-xuan Fu; Yong-liang Zhu; Rong-fu Wang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Potent inhibition of protein tyrosine phosphatases by copper complexes with multi-benzimidazole derivatives - Ying Li; Liping Lu; Miaoli Zhu; Qingming Wang; Caixia Yuan; Shu Xing; Xueqi Fu; Yuhua Mei (BioMetals, 2011)

Noradrenaline regulates substance P release from rat dorsal root ganglion neurons in vitro - Yan-Jie Wang; Xing-Fu Li; Feng Ding; Qiang Shu; Li-Jun Song; Xiao Yu; Hua-Xiang Liu (Neuroscience Bulletin, 2011)

Spectroscopic and Molecular Modeling Studies on the Interaction Between a Fluorine-Containing Triazole Derivative and Human Serum Albumin - Jia-Xin Fu; Yu-Shu Ge; Feng-Lei Jiang; Xiao-Hong Sun; Yang Liu; Yi Liu (Biological Trace Element Research, 2011)

The Impact of Dietary Iodine Intake on Lipid Metabolism in Mice - Shu-Jun Zhao; Yan Ye; Fu-Jun Sun; En-Jiang Tian; Zu-Pei Chen (Biological Trace Element Research, 2011)

Expression of tissue inhibitor of metalloproteinases-3 messenger RNA and protein in porcine endometrium during implantation - Qian Ren; Shu Guan; Jinluan Fu; Aiguo Wang (Molecular Biology Reports, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

A model of BmK CT in inhibiting glioma cell migration via matrix metalloproteinase-2 from experimental and molecular dynamics simulation study - Yue-Jun Fu; Na An; Kok-Gan Chan; Yan-Bo Wu; Shu-Hua Zheng; Ai-Hua Liang (Biotechnology Letters, 2011)

A novel direct equipartition ray design (EquRay) procedure for toxicity interaction between ionic liquid and dichlorvos - Rong-Ni Dou; Shu-Shen Liu; Ling-Yun Mo; Hai-Ling Liu; Fu-Cai Deng (Environmental Science and Pollution Research, 2011)

Mitigating large water ingresses into the New Yungchuen Tunnel, Taiwan - Tai-Tien Wang; Fu-Shu Jeng; Wei Lo (Bulletin of Engineering Geology and the Environment, 2011)

Analyzing coastal wetland change in the Yancheng National Nature Reserve, China - Chang-Qing Ke; Dong Zhang; Fu-Qiang Wang; Shu-Xing Chen; Christance Schmullius; Wolfgang-Martin Boerner; Hui Wang (Regional Environmental Change, 2011)

Cumulate hornblendite enclaves in diorite–porphyrite intrusions from the Shuangyashan, Northeast China, and implications for the transition from lower crust to upper mantle in subduction setting - Lei Zhang; Bao-Fu Han; Chun-Jing Wei; Gui-Ming Shu (International Journal of Earth Sciences, 2011)

Inhibition protein tyrosine phosphatases by an oxovanadium glutamate complex, Na2[VO(Glu)2(CH3OH)](Glu = glutamate) - Liping Lu; Sulian Wang; Miaoli Zhu; Zhiwei Liu; Maolin Guo; Shu Xing; Xueqi Fu (BioMetals, 2010)

Th17 promotes acute rejection following liver transplantation in rats - Xiao-jun Xie; Yu-fu Ye; Lin Zhou; Hai-yang Xie; Guo-ping Jiang; Xiao-wen Feng; Yong He; Qin-fen Xie; Shu-sen Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Patterns of plant invasions in China: Taxonomic, biogeographic, climatic approaches and anthropogenic effects - Shan-Huah Wu; Hao-Ting Sun; Yung-Ching Teng; Marcel Rejmánek; Shu-Miaw Chaw; T.-Y. Aleck Yang; Chang-Fu Hsieh (Biological Invasions, 2010)

Transgenic RNAi-mediated reduction of LZP3 in Lagurus lagurus oocytes results in decreased fertilization ability in IVF - Shu Zhen Zhuang; Xin Jian Li; Ai Lian Zhang; Ji Ma; Yao Hu Zheng; Fu Chun Zhang (Molecular Biology Reports, 2010)

Deformation of lower-mantle ferropericlase (Mg,Fe)O across the electronic spin transition - Jung-Fu Lin; Hans-Rudolf Wenk; Marco Voltolini; Sergio Speziale; Jinfu Shu; Thomas S. Duffy (Physics and Chemistry of Minerals, 2009)

Studying the Interaction of Pirarubicin with DNA and Determining Pirarubicin in Human Urine Samples: Combining Excitation -Emission Fluorescence Matrices with Second-order Calibration Methods - Hong-Yan Zou; Hai-Long Wu; Yan Zhang; Shu-Fang Li; Jin-Fang Nie; Hai-Yan Fu; Ru-Qin Yu (Journal of Fluorescence, 2009)

Sequence Polymorphism and Evolution of Three Cetacean MHC Genes - Shi Xia Xu; Wen Hua Ren; Shu Zhen Li; Fu Wen Wei; Kai Ya Zhou; Guang Yang (Journal of Molecular Evolution, 2009)

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat - Tian-Heng Ren; Zu-Jun Yang; Ben-Ju Yan; Huai-Qiong Zhang; Shu-Lan Fu; Zheng-Long Ren (Euphytica, 2009)

The Avoidance Responses of Daphnia magna to the Exposure of Organophosphorus Pesticides in an On-Line Biomonitoring System - Zong-Ming Ren; Zhi-Liang Li; Jin-Miao Zha; Kai-feng Rao; Mei Ma; Zijian Wang; Rong-Shu Fu (Environmental Modeling & Assessment, 2009)

Development and genetic mapping of microsatellite markers from genome survey sequences in Brassica napus - Xiaomao Cheng; Jinsong Xu; Shu Xia; Jianxun Gu; Yuan Yang; Jie Fu; Xiaoju Qian; Shunchang Zhang; Jiangsheng Wu; Kede Liu (Theoretical and Applied Genetics, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Identification, expression and tissue distribution of a renalase homologue from mouse - Jian Wang; Shaoling Qi; Wei Cheng; Li Li; Fu Wang; Ying-Zi Li; Shu-Ping Zhang (Molecular Biology Reports, 2008)

Trade-offs between constitutive and induced resistance in wild crucifers shown by a natural, but not an artificial, elicitor - Peng-Jun Zhang; Jin-Ping Shu; Cheng-Xin Fu; Yun Zhou; Ying Hu; Myron P. Zalucki; Shu-Sheng Liu (Oecologia, 2008)

Gene transfer into primary cultures of fetal neural stem cells by a recombinant adenovirus carrying the gene for green fluorescent protein - Yong Fu; Shen-qing Wang; Ying-peng Liu; Guo-peng Wang; Jian-ting Wang; Shu-sheng Gong (Journal of Zhejiang University-SCIENCE B, 2008)

Genetic Diversity and Geographic Differentiation in the Threatened Species Dysosma pleiantha in China as Revealed by ISSR Analysis - Min Zong; Hai-Long Liu; Ying-Xiong Qiu; Shu-Zhen Yang; Ming-Shui Zhao; Cheng-Xin Fu (Biochemical Genetics, 2008)

Generation and characterization of two novel low phytate mutations in soybean (Glycine max L. Merr.) - Feng-Jie Yuan; Hai-Jun Zhao; Xue-Liang Ren; Shen-Long Zhu; Xu-Jun Fu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Evaluation of dermal absorption and protective effectiveness of respirators for xylene in spray painters - Fu-Kuei Chang; Mei-Lien Chen; Shu-Fang Cheng; Tung-Sheng Shih; I-Fang Mao (International Archives of Occupational and Environmental Health, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Using EEFM (Excitation Emission Fluorescence Matrix) to Differentiate the Organic Properties of the Effluents from the Ozonated Biofilters - Wen-Liang Lai; Lih-Fu Chen; Shao-Wei Liao; Shu-Lin Hsu; Li-Ho Tseng; Chang-Ling Miaw (Water, Air, & Soil Pollution, 2007)

Generation and characterization of low phytic acid germplasm in rice (Oryza sativa L.) - Qing-Long Liu; Xiu-Hong Xu; Xue-Liang Ren; Hao-Wei Fu; Dian-Xing Wu; Qing-Yao Shu (Theoretical and Applied Genetics, 2007)

Importin KPNA2, NBS1, DNA Repair and Tumorigenesis - Shu-Chun Teng; Kou-Juey Wu; Shun-Fu Tseng; Chui-Wei Wong; Li Kao (Journal of Molecular Histology, 2006)

Species-specific SCAR markers for authentication of Sinocalycanthus chinensis - Qian Ye; Ying-xiong Qiu; Yan-qi Quo; Jian-xin Chen; Shu-zhen Yang; Ming-shui Zhao; Cheng-xin Fu (Journal of Zhejiang University-SCIENCE B, 2006)

Benzo[a]pyrene-induced cell cycle progression is through ERKs/cyclin D1 pathway and requires the activation of JNKs and p38 mapk in human diploid lung fibroblasts - Hong Ju Du; Ning Tang; Bing Ci Liu; Bao Rong You; Fu Hai Shen; Meng Ye; Ai Gao; Chuan Shu Huang (Molecular and Cellular Biochemistry, 2006)

Restoration of Marine Coastal Ecosystem Health as a New Goal for Integrated Catchment Management in Tolo Harbor, Hong Kong, China - Fu-Liu Xu; Jun-Yi Hao; Shu Tao; Richard W. Dawson; K. C. Lam; Yongqin David Chen (Environmental Management, 2006)

Identification and expression analysis of alternatively spliced isoforms of human interleukin-23 receptor gene in normal lymphoid cells and selected tumor cells - Xiang-Yue Zhang; Hai-Jing Zhang; Yun Zhang; Ying-Jie Fu; Jie He; Li-Ping Zhu; Shu-Hui Wang; Li Liu (Immunogenetics, 2006)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Breeding bird species richness in Taiwan: distribution on gradients of elevation, primary productivity and urbanization - Pei‐Fen Lee; Tzung‐Su Ding; Fu‐Hsiung Hsu; Shu Geng (Journal of Biogeography, 2004)
Aim To examine the richness of breeding bird species in relation to elevation, primary productivity and urbanization. Location The island of Taiwan (120°–122° E, 22°–25° N). Methods We arranged bird species richness (BSR) data from 288 bird censuses undertaken in Taiwan into a 2 × 2 km quadrat system and calculated average values of elevation, primary productivity [surrogated by normalized difference vegetation index (NDVI)], and urbanization (surrogated by road density and percentage of built area) for each 2 × 2 km quadrat. Results Bird species richness showed a hump‐shaped relationship with elevation. It increased with elevation from sea level (10–64 species per 2 × 2 km quadrat), peaked around 2000 m (43–76 species), and then decreased with elevation towards its minimum at the highest elevation. Road density and percentage of built area decreased with elevation, and NDVI showed a hump‐shaped relationship with elevation and inverse relationships with road density and percentage of built area. BSR increased with NDVI and decreased with road density and percentage of built area. Linear and cubic terms of elevation together explained 31.3% of the variance in BSR, and road density explained additional 3.4%. The explanatory power of NDVI on BSR was insignificant after the effects of elevation and road density had been justified. Main conclusions We argue that urbanization plays an important role in the BSR of Taiwan. Urbanization might indirectly decrease BSR through decreasing primary productivity and therefore change the hypothetical inverse relationship between BSR and elevation into a hump‐shaped relationship. We also propose a time hypothesis that the biotic communities in the mid‐elevation zone of Taiwan had relatively longer periods of existence during the Pleistocene glacial cycles, which might be one underlying process of the observed hump‐shaped relationship between species diversity and elevation.

Priorities for the conservation of avian biodiversity in China based on the distribution patterns of endemic bird genera - Fu-Min Lei; Yan-Hua Qu; Qian-Qian Tang; Shu-Cheng An (Biodiversity and Conservation, 2003)

A method for lake ecosystem health assessment: an Ecological Modeling Method (EMM) and its application - Fu-Liu Xu; Richard W. Dawson; Shu Tao; Jun Cao; Ben-Gang Li (Hydrobiologia, 2001)

The effects of spaceflight on soluble protein, isoperoxidase, and genomic DNA in ural licorice (Glycyrrhiza uralensis fisch.) - Wen-Yuan Gao; Rong-Zhao Fu; Lei Fan; Shu-Ping Zhao; Kee-Yoeup Paek (Journal of Plant Biology, 2000)

The restoration of riparian wetlands and macrophytes in Lake Chao, an eutrophic Chinese lake: possibilities and effects - Fu-Liu Xu; Shu Tao; Zhuo-Ran Xu (Hydrobiologia, 1999)

Tissue- and stage-specific expression of a soybean (Glycine max L.) seed-maturation, biotinylated protein - Yue-ie C. Hsing; Chih-hua Tsou; Tze-fu Hsu; Zuey-ying Chen; Kim-leong Hsieh; Jaw-shu Hsieh; Teh-yuan Chow (Plant Molecular Biology, 1998)